Selective leaching and separation of aluminum and potassium from alunite by fluorosilicic acid: Kinetics and mechanistic insights - Wen Tan; Yanbo Yang; Junjie Zhang; Chengchao Liu; Yibo Li; Suofeiya Ba; Wei Weng; Xiaopeng Chi; Ni Xiao; Jiaozhong Cai; Shuiping Zhong (Minerals Engineering, 2026)

A novel antifungal potential protein of Bacillus subtilis-fermented Gracilaria agar-processing wastewater: identification, mechanism, regulation and applications in citrus protection - Zhipeng Li; Miaomiao Yang; Xiaoyu Wei; YanYan Wu; Tao Hong; Yuanfan Yang; Mingjing Zheng; Zedong Jiang; Yanbing Zhu; Qingbiao Li; Hui Ni; Xiping Du (Food Microbiology, 2026)

Establishment of the chromid database and analysis of evolutionary research - Yi Liao; Boyan Wang; Yuhui Li; Wei Ni; Xia Li; Shengwei Hu (Molecular Genetics and Genomics, 2026)

Sesquiterpenoids isolated from the leaves of Aucklandia costus and their inhibitory effect on nitric oxide production - Long-Gao Xiao; Tao-Bin He; Yan-Xi Li; Yun Niu; Huan Yan; Hui-Ying Liu; Hui Liu; Wei Ni; Xin Fang; Hai-Yang Liu (Phytochemistry, 2026)

Saebias A–G, eudesmane sesquiterpenes from Salvia plebeia with potential for Alzheimer's disease prevention via anti-neuroinflammatory and neuroprotective effects - Xiao-Die Shu; Han-Fei Liu; Yu-Qiong Liao; Wan-Jun Pu; Ting Zhao; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Repeated recharge of primitive melts in the lower oceanic crust: Constraints from the Dongco ophiolite, Central Tibet - Xiao-Ni Li; Chuan-Zhou Liu; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang (Lithos, 2026)

Investigation of internal force redistribution in shear wall structures subjected to seismic action - Gang Xu; Xiang-yong Ni; Ying-min Li; Wei Jing; Heng-yuan Zhang; Shi-yuan Wang (Soil Dynamics and Earthquake Engineering, 2026)

Effects of evidence-based perineal massage on maternal and neonatal physiological outcomes and childbirth experience in primiparous women: A quasi-experimental study - Yuxuan Li; Linlin Cao; Hongxiao He; Haishan Wei; Hong Lu; Shenglian Ni; Jie Lu; Ruiqing Dong; Mengting Wang; Xiaoding Zhou (Next Research, 2026)

In-situ growth of rGO-PbO2 particles on the surface of RTNAs using surfactant as the structure-directing agent: A synergistic strategy for enhanced degradation of cefuroxime contaminated wastewater - Yue Ni; Yingxia Hu; Jinlong Xu; Huanhuan Zhao; Yashi Liu; Junmei Qin; Chen Yang; Wei Li; Zepeng Sun (Journal of Environmental Chemical Engineering, 2026)

Effects of long-term room temperature storage on phenolic acids and furfurals in honey - Fanhua Wu; Xinyu Wang; Jinkui Wu; Dianli Yang; Chu Li; Ying Zhang; Ni Cheng; Haoan Zhao; Wei Cao (Food Chemistry, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

Early-life exposure to non-optimal temperature and emotional and behavioral problems in preschool children - Rui Li; Jie Ni; Wei Wu; Zhenghong Zhu; Huijun Li; Qingju Meng; Minsi He; Cunrui Huang; Qiong Wang (Environmental Research, 2026)

Natural occurrence of a slow lytic pseudomonas phage in a Pediatric case of multidrug-resistant P. aeruginosa severe pneumonia - Jiaying Sun; Jingru Zhou; Long Wang; Dilare Lidifu; Ping Ni; Qin Li; Xuhua Zhang; Wei Li; Wujin Chen (Virus Genes, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Lactic acid bacterial fermentation enhances the anti-Helicobacter pylori potential of seaweed extracts through compositional transformation - Qiuying Chen; Ling Zhou; Tao Hong; Wei Cai; Mingjing Zheng; Yanbing Zhu; Lijun Li; Zedong Jiang; Hui Ni (Food Bioscience, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

Three new naphthoquinone-based meroterpenoids from Streptomyces sp. HBERC-16614 with antibacterial activities - Ya-Ni Zhang; Man-Li Liu; Fang Liu; Zhi-Gang Zhang; Zhao-Yuan Wu; Li-Qiao Shi; Zhong-Yi Wan; Yue-Ying Wang; Fei Zhang; Kai-Mei Wang; Wei Fang (Natural Product Research, 2026)

Unraveling the different roles of enone oxidoreductases (FaEOs) in strawberry to improve aroma quality during cold storage - Pengpeng Sun; Quanzhi Wang; Yuan Ni; Zhiming Yan; Gang Li; Yuanhua Wang; Wei Chen; Qi Zhou; Pengcheng Zhao; Jialong Cheng; Bingxuan Li; Yuwei Tang; et al. (Postharvest Biology and Technology, 2026)

Critical review of the influence of charge-assisted hydrogen bonding on fate, transport, and treatment of representative contaminants of emerging concern and natural organic matter - Xiaoyun Li; Yue Wang; Baoshan Xing; Marc Teixidó; María A. Cruz; Ran Wei; Jinzhi Ni; Hirotatsu Murano; Zhengyang Wang (Journal of Hazardous Materials, 2026)

Tidal level seasonally modulates sediment organic carbon in seagrass meadows of tropical lagoon bays - Xiao-Ya Zhang; Hui-Jue Luo; Qian-Wei Li; Mu-Qiu Zhao; Zhen Ni; Yun-Feng Shi; Yin-Liu Wang; Yu-Chao Li (CATENA, 2026)

Integrated straw return with tillage and amendments enhances wheat yield by regulating soil properties and microbial communities - Ningqi Wang; Xiaofeng Mai; Yang Gao; Feng Ni; Yichao Hu; Ying Guan; Yikui Wang; Weiliu Li; Zhong Wei; Xinlan Mei; Yangchun Xu; Tianjie Yang (Journal of Soils and Sediments, 2026)

Can waste resource policies boost earnings of green concept stocks? Evidence from waste-to-energy technology - Hui Hu; Yu-Wei Ni; Zhi-Gao Cheng; Xiang Li (Clean Technologies and Environmental Policy, 2026)

Ectoine modulates mixotrophic denitrification pathway partitioning to sustain stable nitrogen and phenol removal under hypersaline stress - Jingwen Song; Ya-Nan Hou; Ran Li; Zengyue Feng; Ai-Jie Wang; Nanqi Ren; Wei Wei; Bing-Jie Ni; Cong Huang (Water Research, 2026)

Global evidence on vitamins in human milk: A 2002–2022 systematic review with a focus on China and implications for maternal diet and infant formula - Yan Yang; Xinggang Ni; Nian Liu; Quanzhang Li; Qi Fang; Ignatius Man-Yau Szeto; Sufang Duan; Teng Wei; Tianyu Rao; Zeyuan Deng; Ting Li; Jing Li (Food Research International, 2026)

Chitosan oligosaccharides activate PPARγ to alleviate aflatoxin B1-induced testicular inflammation and barrier damage - Pei-Yu Dong; Zhuang-Bing Li; Sheng-Lin Liang; Xi-Feng Zhang; Yan-Ni Feng; Wei You (Food Bioscience, 2026)

Synergistic rigid-flexible hybrid interface based on PAA and FeF3 towards dendrite-free lithium-oxygen batteries - Dongxu Yin; Guiru Sun; Daming Yang; Baoxin Ni; Ying Li; Wei Lu; Maobin Wei; Ming Feng (Chemical Engineering Journal, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Spatial confinement effect enhances the activity and thermal stability of Pt/CeO2 for CO oxidation via coating cobalt nitride layer - Min Li; Bifeng Zhang; Lijun Ni; Qi Zhang; Jing Xu; Ying Zhang; Chengsi Pan; Wei Tan; Yongfa Zhu; Fudong Liu; Yang Lou (Chemical Engineering Journal, 2026)

Effects of forest type and elevation on plant and microbial residue carbon concentrations on Kunyu Mountain, China - Wei Zhu; Shiguo Gu; Jinyuan Wang; Tingting Mu; Yanyan Ni; Jun Gao; Mai-He Li (Journal of Soils and Sediments, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

UCHL1-mediated deubiquitination of GLOD4 regulates mitochondrial homeostasis and PTC malignant progression via GLO1 - Lei Cai; Li-Yuan Qian; Wei Wu; Bo-Ni Ding; Zi-Run Luo; Juan Du (Molecular and Cellular Biochemistry, 2026)

Selenylation enhances anti-melanogenic activity of polysaccharide from Cinnamomum cassia Presl. by regulating the CREB/MITF/tyrosinase pathway - Qi-Cong Chen; Ya-Li Wang; Yu Luo; Yan-Ling Zhang; Wen-Xin Li; Wei-Feng Cai; Qian Ni; Cui-Ping Jiang; Qiang Liu; Chun-Yan Shen (Food Research International, 2026)

AIEgens-based polarity/viscosity and ratiometric ONOO− fluorescent probe for tumor imaging, rheumatoid arthritis and Parkinson's disease progression - Peng Lei; Pengjia Wei; Ni Wu; Li Fan; Chuan Dong; Shaomin Shuang; Minglu Li (Chemical Engineering Journal, 2026)

Tailoring nitric oxide-release hydrogel incorporating MSC-derived exosomes for multimodal therapy of diabetic foot ulcers - Kaijie Zhao; Xuan Tian; Qijian Wei; Yuteng Li; Mingzhuo Zhou; Anhui Mu; Xin Yan; Shilei Ni; Pei Liu (Chemical Engineering Journal, 2026)

High-altitude de-acclimatization and long-term immune suppression: the role of Nrf2 in Treg function targeting 3PM - Yuxin Wang; Zhijie Bai; Jiamiao Li; Jinfeng Liu; Yunan Zhang; Xizheng Wang; Lei Zhou; Haoyu Ni; Pan Shen; Ningning Wang; Zhexin Ni; Chaoji Huangfu; et al. (EPMA Journal, 2026)
Background High-altitude de-acclimatization (HADA) is accompanied by a complex spectrum of long-term physiological and functional remodeling processes, potentially affecting long-term health outcomes. Existing studies on HADA have predominantly focused on cardiovascular and nervous system changes. However, the immune system—an essential regulator of disease susceptibility, inter-individual variability, and long-term health risks—remains insufficiently investigated in the context of HADA. Aims Given the central role of immune regulation in maintaining systemic homeostasis and determining individual health trajectories, elucidating immune alterations associated with HADA is essential. The present study aims to characterize immune system remodeling during HADA with particular emphasis on its functional outcomes and mechanisms. By addressing these scientific questions, this study seeks to provide an immune system perspective for the health maintenance of HADA individuals, promoting paradigm shift from reactive medical services toward predictive, preventive, and personalized medicine (3PM). Methods Peripheral blood was collected from both human cohorts and mice models while other immune organs including spleen, thymus and bone marrow were obtained from mice models. Proportions of immune cell populations in peripheral blood and other immune organs were analyzed using flow cytometry. The immune-suppressive functions of Tregs were determined by in vitro co-culture with CD8 + T cells. Transcriptomic and chromatin-accessibility feature induced by HADA were obtained through RNA-seq and ATAC-seq. The functional validation of HADA target gene was performed using specific agonist during in vitro co-culture system. Results HADA perturbed the proportions of immune populations in multiple immune site. Both data from human and mice showed increased regulatory T cells (Tregs) and enhanced immune-suppressive function in the peripheral blood. As a consequence, these Tregs mediated long-term immune suppression and compromised the immunity against tumor cells. Multi-omic analyses predicted Nrf2 as the key mediator of molecular alterations in Tregs caused by HADA, which was further confirmed by the functional assay. Conclusion and expert recommendation This study advances high-altitude medicine by demonstrating that HADA induces long-lasting immunosuppressive effects through Nrf2-mediated Treg remodeling, with important implications for immune homeostasis and long-term health risks. These findings highlight the role of the immune system, particularly Tregs, in HADA-induced health impairments and identify Nrf2 as a potential therapeutic target. Moreover, immune biomarkers—especially Treg phenotypes and Nrf2 activity—may serve as promising candidates for risk stratification and predictive diagnostics in populations transitioning between high- and low-altitude environments. Preventive strategies should prioritize immune-informed recovery protocols, oxidative stress modulation, and lifestyle or nutritional interventions tailored to individual immune profiles.

Bisphenol AP promotes pulmonary fibrosis by regulating macrophage function in a bleomycin-induced mouse model - Ze Chen; Zhenying Lin; Meng Ni; Baihe Li; Qianqian Zhang; Zelin Cao; Wei Li; Yanan Tang; Dongting Yao; Chunyu Cheng; Yi Hu; Xiaorui Liu; et al. (Toxicology, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Oxidized- and hydroxylated-pennogenin saponins from the rhizomes of Paris fargesii and their hemostatic activity - Ling-Ling Yu; Lijin Jiao; Yan-Xi Li; Xu-Hong Li; Shan-Shan Ling; Long-Gao Xiao; Rui-Qi Liu; Wei Ni; Huan Yan; Yunheng Ji; Hai-Yang Liu (Phytochemistry, 2026)

Natural vivianite activates peroxymonosulphate for efficient ofloxacin degradation: Performance and mechanism - Teng Bao; Cheng long Li; Wei Wei; Mekdimu Mezemir Damtie; Zhijie Chen; Haijiao Xie; Bing-Jie Ni (Environmental Research, 2026)

Highly transparent sponge-like hydrogel substrates regulated by NaCl for efficient solar water evaporation - Ke Cheng; Yangyang Li; Hong Ni; Rui Zhang; Wei Wei; Jing Zhou; Jing Yuan (Chemical Engineering Journal, 2026)

Mechanisms and implications of water and nitrogen regulation on soil nitrogen transformation under brackish water irrigation - Yu Wang; Chenchen Wei; Qiangqiang Li; Peiling Yang; Shumei Ren; Lingyun Guo; Ni Zhang (Irrigation Science, 2026)

Spatiotemporal patterns of artificial forest expansion and their driving mechanisms for carbon sink enhancement in China (2005–2019) - Si-Yu Li; Xing-Peng Wei; Yuan Meng; Yu-Ting Yang; Zi-Yi Zheng; Jing-Xuan Zhou; Wang-Bo Yuan; Hong-Gang Ni (Land Use Policy, 2026)

Nonnegligible migration of rubber-derived chemicals from road surface to adjacent greenbelt soil - Zhen-Yu Ge; Hai-Yan Zhang; Xue-E Li; Yue-Hong Liu; Li-Ni Wei; Xiang-Ning Liang; Yan-Feng Lv; Tuan-Tuan Wang; Sai Wang; Jian-Liang Zhao (Journal of Hazardous Materials, 2026)

Synergistic effects of DHA and choline delivered via co-encapsulated microcapsules in infant formula Rice cereal: Enhanced cognitive function and molecular mechanisms in mice - Xinyao Liu; Zuohua Xie; Yuqing Zhang; Meng Wei; Xinggang Ni; Zhang Siqiong; Lu Ling; Sheng Wengsheng; Ting Luo; Jing Li (Food Research International, 2026)

Effects of low-temperature storage on the physiology, biochemistry, and predation ability of Eocanthecona furcellata (Wolff) (Hemiptera: Pentatomidae) - Ling-Yi Liu; Chun-Ni Pan; Meng-Shuang Yao; Wei-Zhou; Zhi-Li Li; Hao-Jun Li; Wen-Long Chen (Phytoparasitica, 2026)

Characterization and Genomic Analysis of the First Phage Infecting Vibrio hyugaensis, vB_VhyS_SJ1 - Suqing Zhang; Wei Wang; Xin Chen; Ziyue Wang; Xiangyun Chen; Zhaobin Zheng; Ni Wang; Yeong Yik Sung; Wen Jye Mok; Li Lian Wong; Min Wang; Hongbing Shao; et al. (Current Microbiology, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Structural identification and antioxidant and hypolipidemic activities of Wurfbainia villosa var. villosa polysaccharides - Minglong Ni; Haosen Feng; Wei Li; Guangqiong Chen; Zhili Liang (Natural Product Research, 2026)

Real-world safety of fruquininib in refractory metastatic colorectal cancer: A cross-database study - Qian Guo; Meirong Shan; Yanhua Fu; Ni Li; Chu Wu; Wei Gao (Regulatory Toxicology and Pharmacology, 2026)

Iridoid glycosides and phenolic glycosides from Gentiana rhodantha and their anti-inflammatory activities - Han-Fei Liu; Wan-Jun Pu; Ting Zhao; Xiao-Die Shu; Jun-Jie Lan; Chao Chen; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Experimental and numerical study on resistance reduction of a polar ship by using water flushing system in broken ice fields - Yunyi Zhang; Bin Fang; Chen Liu; Yanzhuo Xue; Baoyu Ni; Hongyu Wei; Haochun Li (Ocean Engineering, 2026)

Developmental toxicity of carboxylated microplastics in zebrafish mediated by mitochondrial dysfunction and inflammatory activation - Yantong Li; Yuyang Ni; Chenyin Dong; Jiayi Zhang; Hongzhi Guo; Shiyin Zhu; Chaoyi Du; Qi Yu; Zebin Wei; Yajing Han; Shaolin Xie (Environmental Pollution, 2026)

A novel carbon efficiency evaluation method: Why do four-star hotels have more room for carbon efficiency improvement? - Hui Hu; Yu-Wei Ni; Jing-Shu Liu; Xiang Li (Energy and Buildings, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Intra-oceanic arc subduction within the Meso-Tethys Ocean constrained by arc crust remnants in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Xiao-Ni Li; Chang Zhang; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

An integrated Pb isotope-PMF framework for enhanced source apportionment and risk control of heavy metals in soils of a pyrite mining area - Shuai Yan; Mengjing Ni; Kunyu Li; Fei Wei; Qiuyu Huang; Yongxia Jia; Xiaojing Liu; Guiyin Wang; Xiaoxun Xu; Yulin Pu; Shirong Zhang; Ting Li (Journal of Environmental Chemical Engineering, 2025)

Solution mixing approach for advanced iCOFs MMMs exhibiting high-efficiency salt/dye separation and superior membrane stability - Mengzhu Li; Peizheng Ni; Wei Wang; Shusu Shen; Ganwei Zhang; Yongfu Guo (Journal of Environmental Chemical Engineering, 2025)

Negative carbon cementitious materials: Improving performance and CO2 sequestration with carbonated steel slag in solid waste-based systems - Dongdong Zhang; Jiajie Li; Xingtong Yue; Ziping Pan; Yingxi Hu; Wei Su; Wen Ni; Michael Hitch (Journal of Environmental Chemical Engineering, 2025)

Multiscale modelling reveals new insights into the deformation mechanism of rockfill dams - Di Wang; Ni An; Jinfang Hu; Yiao Li; Wei Zhou; Gang Ma (Computers and Geotechnics, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Intensified rainfall overrides vegetation greening in driving erosion and carbon loss on the Tibetan Plateau - Rui Deng; Dongfeng Li; Yi Zhao; Desmond E. Walling; Panos Panagos; Pasquale Borrelli; Philippe Ciais; Yuefei Huang; Yuanyuan Bai; Sergey Chalov; Valentin N. Golosov; Xudong Fu; et al. (Science Bulletin, 2025)

Landscape features and hydrological seasonality control dissolved organic matter and pCO2 variability in a karst river - Yongmei Ma; Junhao Gao; Xunli Wang; Ying Liu; Maofei Ni; Wei Tang; Siyue Li (Journal of Hydrology, 2025)

Crystal-scale heterogeneity of Sn isotopes in Cassiterite: implications for reconstructing ore-forming processes in magmatic-hydrothermal systems - Liang Han; Guo-Guang Wang; Pei Ni; Jun-Yi Pan; Jia-Xin She; Wei Tan; Weiqiang Li (Geochimica et Cosmochimica Acta, 2025)

Experimental and numerical study on the fire resistance behavior of steel truss girder structure in double deck suspension bridges - Zongxing Zhang; Yuxuan Xu; Yuwei Li; Wei Chen; Jihong Ye; Mingchun Wu; Ya Ni; Jian Jiang (Engineering Structures, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Enabling high-performance aqueous Zn batteries with sub-zero temperatures surpassing room temperature combining cosolvent engineering and redox regulation strategy - Qiong Li; Ganghui Wei; Ni Lan; Yanzheng Li; Libo Wang; Xinyu Zhang; Yujun Fu; Qiming Liu; Yonggang Zhao; Deyan He (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Pilot-scale non-sterile mixotrophic cultivation of Galdieria sulphuraria for high-efficient removal of ammonium with enhancing high-protein biomass production from industrial effluent - Yu Li; Dong Wei; Xiannan Peng; Hao Shen; Li Ni; Guoyou Wei (Bioresource Technology, 2025)

A mutation in CmoBADH results in the production of 2-acetyl-1-pyrroline, conferring a ‘taro-like’ aroma in Cucurbita moschata - Gangjun Zhao; Liting Deng; Xiaoxi Liu; Haibin Wu; Jianning Luo; Hao Gong; Xiaoming Zheng; Xueting Wang; Zuyun Dai; Chaoqun Ni; Xiaoshan Wei; Caixia Luo; et al. (Theoretical and Applied Genetics, 2025)

Mn-doped carbon dots-based fluorescent-colorimetric dual-mode probes for selective and sensitive detection of Cr(VI) ions and l-ascorbic acid via smartphone-integrated analytical platform - Shan Huang; Wenqian Zhang; Bo Li; Guixin Li; Wei Ni; Yi Fang; Fuxiang Wei; Qi Xiao (Analytica Chimica Acta, 2025)

BDE-47 induces oxidative stress and apoptosis by interfering with pyruvate and glutathione metabolism in Epinephelus coioides - Zongfu Chen; Lei Yan; Peng Luo; Ziyang Xu; Tongwen Ni; Li Lin; Wei Zhang; Yanan Li (Aquaculture International, 2025)

An undescribed ferulic acid ester from Oreocome striata (DC.) Pimenov & Kljuykov and its anti-inflammatory activity - Zixian Xie; Rongrong Li; Yong Xue; Changzhou Wang; Guanghui Yang; Fuyong Ni; Wei Xiao (Natural Product Research, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

Novel acidified red mud-based MnS/FeAl-MOF as three-dimensional electrodes for the activation of peroxymonosulfate to efficient remove gatifloxacin in the photo-electrocatalytic system: Synthesis, influencing factors, and degradation mechanism - Ni Wang; Linye Zhang; HongJiang Li; Yuliang He; Yuhang Ji; Junchi Gu; Guangtao Wei; Guotao Cao (Journal of Environmental Chemical Engineering, 2025)

Freeze-thaw and dry-wet alternation regulate the impacts of Fe-C based passivator on soil heavy metals immobilization - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Environmental Chemical Engineering, 2025)

Tenebrio molitor powder enhances gelation properties of Penaeus vannamei myofibrillar protein: Mechanistic insights into structural optimization and digestibility - Mingfeng Xu; Ruixi Li; Mengting Li; Chaoyi Duan; Yinyin Wei; Xiangxiang Ni; Xiu Wang; Sida Fu; Rongrong Yu (Food Chemistry, 2025)

Dual role of oxygen vacancies in TiO2/Bi2O3 for enhanced carrier separation and PDS activation: A combined experimental and DFT study - Xing-Peng Wei; Yu-Ting Yang; Si-Yu Li; Yuan Meng; Wang-Bo Yuan; Hong-Gang Ni (Environmental Research, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Unsupervised SAM segmentation of zebrafish body: Application to melanin analysis - Yuan Meng; Jing-Xuan Zhou; Yu-Ting Yang; Xing-Peng Wei; Si-Yu Li; Hong-Gang Ni (Environmental Pollution, 2025)

Cold crystallization-enabled permanent shape transformation in 4D-printed PLA/TPU composites for personalized wearable devices - Chuanru Zheng; Xi Li; Juan Tan; Anna Tan; Xiuchen Li; Hailiang Ni; Wenhao Yu; Yuefeng Bai; Ping Hu; Wei Min Huang; Hongmei Chen (Chemical Engineering Journal, 2025)

Mechanically responsive self-reinforced polyurethane elastomers with cyclodextrin metal-organic framework structure for high impact resistance - Jing Lv; Xiaodong Li; Ni Zhai; Tianhao Wu; Chengwang Shi; Hong Yu; Wei Zhang; Tenglong Ma; Hao Jiang; Meishuai Zou (Chemical Engineering Journal, 2025)

Harnessing nanomaterial-driven electron transfer for enhanced uranium recovery and toxicity mitigation in bioelectrochemical systems - Meng Li; Leyi Chen; Kengqiang Zhong; Haowen He; Xing Chen; Xing Lu; Chengjun Guo; Luoyi Han; Ziyin Xia; Chenxi Li; Jingyi Wang; Wei Han; et al. (Bioresource Technology, 2025)

Reduced Usage of GLS Intronic Polyadenylation Promotes Cellular Senescence - Xueping Li; Yuxin Li; Dong Ding; Baiyun Xie; Jun Yao; Yu Chen; Zhaozhao Zhao; Peng Yu; Shengwei Zhang; Fu Yang; Ting Ni; Gang Wei (Phenomics, 2025)

Two novel 5,5-spiroketal sesquiterpenoid isomers from the roots of Angelica biserrata (R. H. Shan &Yuan) C. Q. Yuan & R. H. Shan - Fuyong Ni; Rongrong Li; Zixian Xie; Ying Li; Ningning Xu; Xuanyu Mu; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Xue Xie; Wei Xiao (Natural Product Research, 2025)

Closed-loop ammonium removal enabled by EPS-based hydrogel derived from cyanobacterial blooms - Yu Huang; Xing Zhang; Xiaoying Lv; Jingyi Zhao; Ni Xie; Tingting Dong; Zeng He; Mingyan Qin; Bo Wei; Yalin Li (Process Safety and Environmental Protection, 2025)

Saleucanes A-J, structurally diverse neo-clerodane diterpenoids from Salvia leucantha with anti-neuroinflammatory activity via TLR4/MYD88/NF-κB pathway - Fen-Cong Pan; Han-Fei Liu; Xiao-Die Shu; Xiao-Qiao Yang; Hua-Yong Lou; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2025)

Recycling ancient refractory peridotites causing the crust-mantle decoupling of the Xigaze ophiolite (South Tibet): New constraints from the Buma mantle massif - Jia-Ning Zhu; Chuan-Zhou Liu; Wei-Qi Zhang; Tong Liu; Chang Zhang; Xiao-Ni Li; Zhen-Yu Zhang (Lithos, 2025)

Insights into bridging hydroxyl groups to enhance the efficient-generation of hydroxyl radicals for microplastic decomposition - Zehao Li; Boqiang Gao; Shuanglong Ma; Kai Wang; Jingyi Wei; Shengjun Xu; Yan Huang; Jia Song; Xiaodan Tang; Jingzhen Wang; Sihui Zhan; Bing-Jie Ni (Journal of Cleaner Production, 2025)

Deciphering the aged composite microplastics alleviates methanogenesis inhibitions in anaerobic digestion: The neglected microplastic eco-coronas and microbial electron transfer - Tao Liu; Yu Tian; Junjie Chen; Yuqing Mao; Guiyuan Cai; Yimeng Jiao; Lipin Li; Wei Zuo; Bing-Jie Ni (Chemical Engineering Journal, 2025)

Deciphering the UAV-LiDAR contribution to vegetation classification using interpretable machine learning - Tao Huang; Lei Jiao; Yingfei Bai; Jianwu Yan; Xiping Yang; Jiayu Liu; Wei Liang; Da Luo; Liwei Zhang; Hao Wang; Zhaolin Li; Zongshan Li; et al. (Computers and Electronics in Agriculture, 2025)

Prediction of resistance reduction for ice-going ships installed with air-bubbling systems - Hongyu Wei; Baoyu Ni; Zhiyuan Li (Cold Regions Science and Technology, 2025)

High-efficiency ammonium recovery and high biomass yield from ultrahigh-ammonium industrial effluent via online-controlled photo-fermentation with thermoacidophilic Galdieria sulphuraria - Yu Li; Dong Wei; Xiannan Peng; Hao Shen; Li Ni; Guoyou Wei (Algal Research, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Suppression of TaHDA8-mediated lysine deacetylation of TaAREB3 acts as a drought-adaptive mechanism in wheat root development - Zehui Liu; Qun Yang; Xingbei Liu; Jinpeng Li; Lei Zhang; Wei Chu; Jingchen Lin; Debiao Liu; Danyang Zhao; Xiao Peng; Chaowu Zeng; Mingming Xin; et al. (Molecular Plant, 2025)

Large Zn isotope variations in lower oceanic crust offer insights into oceanic crustal magma plumbing system - Wei-Qi Zhang; Chuan-Zhou Liu; Zong-Qi Zou; Xiao-Ni Li (Geochimica et Cosmochimica Acta, 2025)

Efficient visual detection of sodium nitrite based on redox-responsive photonic crystal sensors - Juan Wei; Jingjing Xu; Chuyi Wang; Ya-Fei Yang; Yue Zhang; Runyan Ni; Yong-Quan Xu; Dejian Huang; Lu Li (Chemical Engineering Journal, 2025)

Stress-relieved synergistic structure engineering achieving robust monolithic porous silicene sheets from micro-sized siloxene for high-rate and high-energy lithium-ion batteries - Juan Geng; Hengtao Shen; Zhengran Wang; Zhiwei Ni; Chuanliang Wei; Yuan Li; Kangdong Tian; Xinlu Zhang; Shenglin Xiong; Jinkui Feng (Chemical Engineering Journal, 2025)

An innovative red-emitting nickel-doped carbon dot for simultaneous detection of Fe(III) and pyrophosphate ions, coupled with synergistic photothermal/photodynamic cancer therapy - Shan Huang; Wenqian Zhang; Bo Li; Guixin Li; Wei Ni; Yi Fang; Qi Xiao (Analytica Chimica Acta, 2025)

Mechanism of adaptive laboratory evolution for improving polyunsaturated fatty acid biosynthesis in Aurantiochytrium sp. through enhancing high-glucose adaptability - Zhipeng Li; Danling Tang; Lifen He; Yuanzhen Song; Wei Hang; Huipeng Liu; Guoxiang Chi; Tao Hong; Hui Ni; Qingbiao Li; Zhen Chen; Ning He (Algal Research, 2025)

Epidemiological characteristics of human parainfluenza virus infections and phylogenetic analysis of human parainfluenza virus type 3 isolated from children with respiratory tract infections from 2020 to 2022 in Zhejiang, China - Yun Lu; Jili Ni; Shuangshuang Huang; Yajun Guo; Yingying Chen; Shufa Zheng; Yingshuo Wang; Wei Li (Archives of Virology, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Comparative lipidomics analysis of human colostrum, mature milk and yak mature milk - Mengmei Ni; Linlan Peng; Yuanyuan Zhang; Liang Wang; Qijie Wei; Xiaomeng Li; Lishi Zhang; Jinyao Chen (Food Chemistry, 2025)

Mantle evolution beneath a back-arc basin: Highly siderophile elements and Os isotope of Dongco ophiolitic peridotites, Tibet - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang; Jia-Ning Zhu; Hong-Yu Li; Chuan-Zhou Liu (Chemical Geology, 2025)

Modulating JAK2/STAT3 signaling by quercetin in Qiling Baitouweng Tang: a potential therapeutic approach for diffuse large B-cell lymphoma - Xin-Zhuo Zhan; Tian-Hua Wei; Chen Huang; Hui Yu; Xiao-Li Chen; Xiang-Tu Kong; Zhi-Hao Shang; Shan-Liang Sun; Meng-Yi Lu; Hai-Wen Ni (Molecular Diversity, 2025)

Rapid identification of multiplexed pathogens via a two-step dual-channel fluorescence turn-on array - Xingliang Huang; Yang Yu; Huihai Li; Zhongzheng Xiong; Jinwu Wei; Dengqiong Yu; Hengfei Zhao; Liya Liao; Yong Li; Chao Guo; Chao Xu; Weiwei Ni; et al. (Analytica Chimica Acta, 2025)

Solasodine binds to glucocorticoid receptor to ameliorate airway remodeling and excessive autophagy in bronchial smooth muscle cells for allergic asthma - Zhen Guo; Jun-li Liu; Yan-ni Fang; Xiao-man Guo; Chun-long Ma; Jing-wei Wang (Toxicology and Applied Pharmacology, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

No association between SARS-CoV-2 infection and embryo chromosomal abnormalities: a prospective cohort study - Tianxiang Ni; Yang Liu; Weiran Cui; Siying Chen; Hongchang Li; Yueting Zhu; Wenjie Jiang; Qian Zhang; Wei Zhou; Zi-Jiang Chen; Yan Li; Guangyong Zhang; et al. (Science China Life Sciences, 2025)

Effect of ridge tillage with rice-rape rotation on the root system and yield of crops - Wenqi Zhang; Lanting Li; Bo Liu; Juan Liu; Fangxin Chen; Jiupai Ni; Chaofu Wei; Shouqin Zhong (Plant and Soil, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Fe/Co-Layered hydroxide-derived mixed metal oxides for efficient conversion of polystyrene to sustainable aviation fuel substitute components under CO2 mediation - Haifeng Jiang; Wei Jia; Jiaxing Song; Meng Song; Zongyuan Zhang; Jiaxin Wang; Zhenjia Ni; Yuhang Li (Chemical Engineering Journal, 2025)

Identification and validation of a major QTL, QFhb-6AL, for Fusarium head blight resistance on chromosome 6AL in wheat - Zhenzhen Zhu; Xuecheng Zhu; Na Zhang; Wenxi Wang; Jilu Liu; Fuping Zhang; Xiaomeng Ren; Yanpeng Ding; Fangyao Sun; Xi He; Sijia Hu; Xiuhua Li; et al. (Theoretical and Applied Genetics, 2025)

Gut microbiota’s role in high-altitude cognitive impairment: the therapeutic potential of Clostridium sp. supplementation - Wei Zhou; Yongqiang Zhou; Shikun Zhang; Bin Li; Zhong Li; Zhijie Bai; Dezhi Sun; Chaoji Huangfu; Ningning Wang; Tiantian Xia; Congshu Huang; Lina Guan; et al. (Science China Life Sciences, 2025)

The effects of temperature and light intensity on the growth and photosynthetic physiology of Pyropia kinositae - Ni Su; Qiuhan Lv; Juntian Xu; Guoqiang Chen; Wei Zhou; Futian Li; Xinshu Li (Journal of Applied Phycology, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Acute mountain sickness prediction: a concerto of multidimensional phenotypic data and machine learning strategies in the framework of predictive, preventive, and personalized medicine - Wenhui Li; Meng Zhang; Yangyi Hu; Pan Shen; Zhijie Bai; Chaoji Huangfu; Zhexin Ni; Dezhi Sun; Ningning Wang; Pengfei Zhang; Li Tong; Yue Gao; et al. (EPMA Journal, 2025)
Background Acute mountain sickness (AMS) is a self-limiting illness, involving a complex series of physiological responses to rapid ascent to high altitudes, where the body is exposed to lower oxygen levels (hypoxia) and changes in atmospheric pressure. AMS is the mildest and most common form of altitude sickness; however, without adequate preparation and adherence to ascent guidelines, it can progress to life-threatening conditions. Aims Due to the multi-factorial predisposition of AMS among individuals, identifying AMS biomarkers before high altitude exposure from multiple dimensions (e.g., clinical, metabolic, and proteomic markers) and integrating them to build an AMS predictive model enables early diagnosis and personalized interventions, which allows targeted allocation of medical resources, such as prophylactic medications (e.g., acetazolamide) and supplemental oxygen, to those who need them most and prevention of unnecessary complications. Consequently, predicting AMS utilizing biomarkers from multidimensional phenotypic data before high-altitude exposure is essential for the paradigm change in high-altitude medical research from currently applied reactive services to the cost-effective predictive, preventive, and personalized medicine (PPPM/3PM) in primary (reversible damage to health and targeted protection against health-to-disease transition) and secondary (personalized protection against disease progression) care. Methods To this end, this study recruited 83 Han Chinese male volunteers and obtained clinical, proteomic, and metabolomic profiles for analysis before they ascended to high altitudes. The Mann–Whitney U test was used to identify clinical features distinguishing AMS from non-AMS. The proteomic and metabolomic features were concatenated and clustered to find co-expression modules associated with AMS. A machine learning model, Mutual Information-radial kernel-based Support Vector Machine-Recursive Feature Elimination (MI-radialSVM-RFE) was employed for biomarkers selection and AMS prediction. A molecular docking technique was used to select molecular biomarkers that can bind with Traditional Chinese Medicine (TCM) ingredients. Results Among 83 participants, 66 were selected for detailed analysis after quality control steps. Six protein-metabolite co-expression modules were identified as significantly associated with AMS. The MI-radialSVM-RFE model selected 12 biomarkers (two clinical features: systolic blood pressure (SBP) and peak expiratory flow (PEF); six proteins: Acyl-CoA synthetase long-chain family member 4 (ACSL4), immunoglobulin kappa variable 1D-16 (IGKV1D-16), coagulation factor XIII B subunit (F13B), prosaposin (PSAP), poliovirus receptor (PVR), and multimerin-2 (MMRN2); and four metabolites: 2-Methyl-1,3-cyclohexadiene, calcitriol, 4-Acetamido-2-amino-6-nitrotoluene, and 20-Hydroxy-PGE2) for the AMS prediction model. The model exhibited excellent predictive performance in both training ( n = 66) and validating cohorts ( n = 24) with AUCs of 0.97 and 0.94, respectively. Additionally, molecular docking analysis suggested PSAP and ACSL4 proteins as potential molecular targets for AMS prevention. Conclusion and expert recommendations This study advances high-altitude medicine by developing a predictive model for AMS using clinical, proteomic, and metabolomic data. The identified biomarkers linked to energy metabolism, immune response, and vascular regulation offer insights into AMS mechanisms. High-altitude predictive approaches should focus on implementing biomarker-driven risk screening using clinical, proteomic, and metabolomic data to identify high-risk individuals before high-altitude exposure. Preventive measures should prioritize pre-acclimatization protocols, tailored nutritional strategies and interventions guided by biomarker profiles, and lifestyle adjustments, such as maintaining mitochondrial health through proper nutritional strategies.

Revealing the underestimated role of Gram-positive bacteria in iron reduction within paddy soils - Yu Huang; Yuquan Tan; Lin Shen; Chao Peng; Yaying Li; Juntao Zhang; Fengrong Zhang; Chunlin Ni; Wei Liu; Yundang Wu; Fangbai Li (Science of The Total Environment, 2025)

Efficiently selective inactivation of Gram-positive bacteria by MCM-41 molecular sieve-supported copper-based self-cascading nanozymes - Xue-Yao Pang; Fan-Xiang Meng; Cheng Ma; Si-Yang Ni; Zi-Han Jia; Bo Li; Yu-Xiang Liu; Wei-Wei Gao (Chemical Engineering Journal, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Wheat2035: Integrating pan-omics and advanced biotechnology for future wheat design - Yingyin Yao; Weilong Guo; Jinying Gou; Zhaorong Hu; Jie Liu; Jun Ma; Yuan Zong; Mingming Xin; Wei Chen; Qiang Li; Zihao Wang; Ruijie Zhang; et al. (Molecular Plant, 2025)

Remnants of a Jurassic marginal sea plate in the Meso-Tethyan Ocean revealed by multi-stage magmatism in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Xiao-Ni Li; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

Integrated microbiome and metabolomics analysis of spoilage characteristics of modified atmosphere packaged pork - Xueya Wang; Ping Li; Xingguang Chen; Wei Cui; Shenyu Ni; Huaxing Xu; Yujuan Xu; Kezhou Cai; Hui Zhou; Baocai Xu (Food Research International, 2025)

Toxicological interactions of cosmetic and personal care additives mixtures: An update based on measurement and simulation - Yu-Ting Yang; Zi-Yi Zheng; Xing-Peng Wei; Yuan Meng; Jing-Xuan Zhou; Si-Yu Li; Wang-Bo Yuan; Hong-Gang Ni (Environmental Research, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Dual regulation of As release and soil environment by Fe(Ⅱ) assisted steel slag and coal fly ash: Effects and potential mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Hazardous Materials, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

High-performance biomass moisture-electric generators derived from Distillers’ spent grains: Synthesis, photothermal enhancement, and environmental sensing applications - Haichuan Gao; Zihao Feng; Wenjun Li; Jiatian Zhu; Shengdong Mu; Hongkai Zhang; Genqiao Liu; Wei Zhao; Bailiang Xue; Yonghao Ni (Chemical Engineering Journal, 2025)

Mussel-inspired highly adhesive carrageenan-based coatings with self-activating enhanced activity for meat preservation - Yumeng Li; Yongsheng Ni; Wei He; Haoran Li; Wendi Zhang; Lijun Tan; Jinsong Zhao; Baocai Xu (Carbohydrate Polymers, 2025)

IL-33 aggravates extranodal NK/T cell lymphoma aggressiveness and angiogenesis by activating the Wnt/β-catenin signaling pathway - Mingli Ni; Yuhui Wang; Jiezhi Yang; Qianwen Ma; Wei Pan; Yulin Li; Qian Xu; Hongqiong Lv; Yunlong Wang (Molecular and Cellular Biochemistry, 2025)

Crustal silica content of East China: A seismological perspective and its significance - Ziwen Bao; Xiaohui Yuan; Wei Li; Yuan Gao; Xianliang Huang; Dequan Hong; Hongyu Ni (Tectonophysics, 2024)

Control of arsenic methylation in paddy soils by iron nanoparticles - Tianhang Gu; Zhuobiao Ni; Qingqing Zhao; Ruofan Li; Rongliang Qiu; Wei-xian Zhang (Science of The Total Environment, 2024)

Effects of land use and dissolved organic matter on pCO2 are dependent on stream orders and hydrological seasonality in a low-order karst river - Yongmei Ma; Maofei Ni; Shijie Gu; Liuqing Zhang; Huaiwei Sun; Wei Tang; Siyue Li (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Source-risk and uncertainty assessment of trace metals in surface sediments of a human-dominated seaward catchment in eastern China - Fangli Wang; Zihan Yu; Yali Zhang; Runxiang Ni; Zhi Li; Shaojing Li; Ningning Song; Jun Liu; Haiying Zong; Wei Jiao; Hongtao Shi (Journal of Hazardous Materials, 2024)

A novel process for recovery of vanadium and chromium from vanadium-chromium sludge: Roasting pretreatment and thermal reduction co-alloying process - Xiong Li; Peiyuan Ni; Tengfei Deng; Xiaodong Hou; Wei Gao; Ying Li (Journal of Cleaner Production, 2024)

Amino modified nanofibers anchored to Prussian blue nanoparticles selectively remove Cs+ from water - Shanshan Feng; Jingshuai Gao; Shouzhu Li; Xun Cao; Jie Ni; Xiuli Yue; Wei Zheng; Yuyao Li; Xueqi Hu; Yao Zhang; Sheng Feng (Journal of Environmental Sciences, 2024)

Comparative analysis of lipid composition in colostrum and mature milk from women of seven Chinese ethnic groups - Zhiyi Zhang; Teng Wei; Xinggang Ni; Ting Li; Ignatius Man-Yau Szeto; Sufang Duan; Yalu Yan; Wenhui Ye; Jing Li; Zeyuan Deng (International Dairy Journal, 2024)

Sericin peptides alleviate dextran sulfate-induced ulcerative colitis symptoms by modulating the Th17 cell differentiation pathway in C57BL/6 mice - Hongtao Zhu; Zhi-Jing Ni; Qian Zhong; Wei Wang; Ya-Jing An; Kiran Thakur; Jian-Guo Zhang; Zhong-Li Chen; Zhao-Jun Wei (Food Bioscience, 2024)

Fe (hydr)oxides and organic colloids mediate colloid-bound chromium mobilization in Cr(VI) contaminated paddy soil - Ting Liu; Ran Wei; Jingjing Li; Weipeng Xie; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Environmental Pollution, 2024)

Asymmetric coordinative modulation boosting the activity and thermal stability of Pt1/CeO2 for CO oxidation under harsh condition - Lijun Ni; Yuwei Zhou; Wei Tan; Hong Li; Dong Wang; Qi Zhang; Bing Yang; Jing Xu; Ying Zhang; Chengsi Pan; Yongfa Zhu; Fudong Liu; et al. (Chemical Engineering Journal, 2024)

rAAV-CRISPR/Cas9-mediated in vivo delivery of porcine embryos to construct knockout pigs - Mengyu Gao; YuTing He; XingLong Zhu; WanLiu Peng; Xinmei Liu; Yanyan Zhou; Yang Deng; Qin Liu; Guangneng Liao; Yi Li; Wei Ni; Guang Yang; et al. (Science China Life Sciences, 2024)

Growth and metabolism regulation of cinnamic acid and its derivatives to Auxenochlorella pyrenoidosa - Min Li; Zhen-Fang Shang; Zhi-Jing Ni; Hui-Jun Zhao; Qian Lei; Zhao-Jun Wei (Algal Research, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Adsorption behavior of heavy metals onto microplastics derived from conventional and biodegradable commercial plastic products - Po-Wen Chen; Man-Ni Hsiao; Li-Wei Xiao; Zhen-Shu Liu (Science of The Total Environment, 2024)

Photobiomodulation ameliorates ovarian aging by alleviating oxidative stress and inflammation damage and improving mitochondrial function - Yu He; Rongan Ye; Yinbo Peng; Qing Pei; Lei Wu; Caixia Wang; Wei Ni; Ming Li; Yiqiu Zhang; Min Yao (Journal of Photochemistry and Photobiology B: Biology, 2024)

Impact resistance and performance of precast shear walls with various connections under axial and lateral loads - Yun Zhou; Xin Zhang; Fan Yi; Jing-Ming Sun; Jia Ni; Ting Li; Wei-Jian Yi (Engineering Structures, 2024)

Mechanistic insights into the roles of copper in enhanced peroxymonosulfate activation for tetracycline degradation by copper ferrite composite catalyst - Jinsong He; Licui Feng; Taoran Shi; Fan Ni; Li Zhao; Yongjia Lei; Yan Liu; Dexin Fang; Zongsu Wei; Fei Shen (Chemical Engineering Journal, 2024)

A superior material with antithrombotic properties serves as a secure adsorbent for the elimination of bilirubin in vitro and in pig models - Rui Su; Wei Liu; Gang Shi; Dongling Chen; Lihua Yan; Qian Li; Haichao Ni; Meili Yu; Liang Xu (Chemical Engineering Journal, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

Pupillometry reveals hyper-arousal in response to auditory stimuli in autistic children - Ci Song; Runsheng Ma; Wei Ni; Xinyue Peng; Xue Li; Ruoxi Shi; Yuanping Zhang; Li Yi (Journal of Zhejiang University-SCIENCE B, 2024)

Low-grade systemic inflammation links heavy metal exposures to mortality: A multi-metal inflammatory index approach - Yin Wang; Yuyan Wang; Ruizhen Li; Baiwen Ni; Ruixin Chen; Yun Huang; Rongrong Cheng; Pei Li; Han Li; Yang Peng; Xue Chen; Jingyu Wang; et al. (Science of The Total Environment, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Exploring the impact of sustainable finance on carbon emissions: Policy implications and interactions with low-carbon energy transition from China - Wei Zhang; Jie Han; Shiyi Kuang; Cem Işık; Ya Su; Gu Li Ni Ga Er Ju Lai Ti; Su Li; Zebang Xia; Anas Muhammad (Resources Policy, 2024)

Retraction notice to “N-rich and O-poor doped carbon prepared via facile ammonium nitrate assisted hydrothermal carbonization for robust supercapacitors” [J Clean. Prod. (2022) 133903] - Xue-Qin Ma; Bo Zhang; Zhi-Xiang Xu; Yi Tan; Bin Li; Yong-Cai Zhang; Guo-Song Ni; Wei-You Zhou; Rafael Luque; Hui-Yan Zhang (Journal of Cleaner Production, 2024)

Remediation of As, Sb, and Pb co-contaminated mining soils by using Fe/C based solid wastes: Synergistic effects and field applications - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Wen Ni; Siqi Zhang; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

Interpreting the removal behaviours of aniline and 3,4-diaminotoluene on aromatic carbon-rich magnetic polymer: Statistical modelling, DFT quantitative calculations and new perspectives - Zhengwen Wei; Liuqing Li; Wei Wang; Wankui Ni; Xiang-fei Lü; Giuseppe Mele; Zhen-Yi Jiang (Chemical Engineering Journal, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Isolation and characterization of forty-two polymorphic simple sequence repeat markers from Mastacembelus armatus (Symbranchiformes: Mastacembelidae) - Laifu Luo; Liqin Ji; Congcong Wu; Wei Li; Xiaoli Liu; Xiaoyou Hong; Xinping Zhu; Yijun Ni; Jiansong Li; Chen Chen; Jiping Zhang (Conservation Genetics Resources, 2024)

Neurotoxic effects of triclosan in adolescent mice: Pyruvate kinase M2 dimer regulated Signal transducer and activator of transcription 3 phosphorylation mediated microglia activation and neuroinflammation - Ziyun Wei; Xiao Ni; He Cui; Chang Shu; Yuxuan Peng; Yunwei Li; Jieyu Liu (Science of The Total Environment, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Inclusion of reeling wastewater-derived sericin peptides in high-protein nutrition bars for antihardening and storage stability - Hongtao Zhu; Zhi-Jing Ni; Kiran Thakur; Jian-Guo Zhang; Zhong-Li Chen; Mohammad Rizwan Khan; Zhao-Jun Wei (Food Chemistry, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Erratum to “CO2-induced reconstruction for ORR-enhanced solid oxide fuel cell cathode” [Chem. Eng. J. 462 (2023) 142216] - Yuan Zhang; Junbiao Li; Heping Xie; Zhipeng Liu; Suling Shen; Ying Teng; Daqin Guan; Shuo Zhai; Yufei Song; Wei Zhou; Bin Chen; Meng Ni; et al. (Chemical Engineering Journal, 2024)

Three undescribed coumarins from the roots of Angelica pubescens - Fuyong Ni; Xue Xie; Xue Huai; Xiao Yu; Hongda Zhang; Ming Li; Jianhui Wen; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2024)

Fine-mapping of LrN3B on wheat chromosome arm 3BS, one of the two complementary genes for adult-plant leaf rust resistance - Weidong Wang; Huifang Li; Lina Qiu; Huifang Wang; Wei Pan; Zuhuan Yang; Wenxin Wei; Nannan Liu; Junna Sun; Zhaorong Hu; Jun Ma; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2024)

The characteristics of nutrient distribution and influencing factors in the Chukchi Plateau and adjacent waters - Zhixin Ni; Han Zhang; Minxia Zhang; Tuanjie Li; Shengyong Li; Xin Chen; Ling Zhang; Yuan Gao; Changshu Chen; Zhongyuan Wang; Wei Deng; Hai zhou Zhang (Frontiers in Marine Science, 2024)
The Arctic is one of the regions under the most dramatic climate change. Global warming has led to elevated freshwater inflow into the western Arctic Ocean and significantly altered nutrient structure and biogeochemical cycling. In this work, inorganic dissolved nutrients in the Chukchi Plateau (CP) and adjacent regions were investigated to further understand their characteristics and influencing factors. Results showed that relatively high nutrient concentrations occurred in the water masses with salinity >32 psu, especially there was a nutrient-rich layer influenced by Winter Pacific Water in the water column (15.10±1.96, 2.23±0.26, and 23.46±6.64 µmol/L for DIN, PO 4 3– and Si(OH) 4 , respectively). Contrarily, lower nutrient concentrations occurred in the mixing water of the upper layer (1.76±1.04, 1.15±0.16 and 3.76±2.29 µmol/L for DIN, PO 4 3– and Si(OH) 4 , respectively) with a low DIN/P ratio (1.44±0.59), suggesting DIN has become the potentially biological limiting factor. Furthermore, the freshening and deepening of the upper layer driven by the Beaufort Gyre has hindered the nutrient transport from underlying layer into the upper layer. A maximum chla was observed at 36‒75 m water depth, and the phytoplankton biomass decreased from the western to the eastern CP, accompanied by a decreased contribution of micro-sized chla but an increased contribution of small-sized chla (74.0±0.1%). The phytoplankton resource use efficiency for DIN was estimated as (3.2±4.6)×10 -3 , which was primarily influenced by the physicochemical parameters of water and also largely regulated by the size structure of phytoplankton.

How do contextual factors mediate and moderate the association between green infrastructure and respiratory health? A systematic review and meta-analysis - Tianyuan Shou; Ke Li; Yongjun Li; Yuchun Ni; Dongdong Lu; Jiaxing Wei (Urban Forestry & Urban Greening, 2024)

Treatment of low-C/N nitrate wastewater using a partial denitrification-anammox granule system: Granule reconstruction, stability, and microbial structure analyses - Lifang Liu; Wei-Kang Qi; Li Zhang; Shu-Jun Zhang; Shou-Qing Ni; Yongzhen Peng; Cong Wang (Journal of Environmental Management, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Molecular Characterization and Potential Host-switching of Swine Farm associated Clostridioides difficile ST11 - Jiewen Huang; Tinghua Li; Yongzhang Zhu; Qingtian Li; Chih-Jung Kuo; Xiaokui Guo; Beiwen Wei; Peihua Ni; Ke Dong (Veterinary Microbiology, 2024)

Holocene Neolithic human activity shaped ecosystem functions through the altering of vegetation traits in Zhejiang, eastern China - Haoyan Wang; Yili Jin; Kai Li; Mengna Liao; Yan Liu; Chunmei Ma; Wei Ye; Yun Zhang; Yongkai Luo; Jian Ni (Quaternary Science Reviews, 2024)

Catalytic hydroconversion of aryl ethers to polycyclic alkanes over Ni@MCM-41/β composite zeolite: Aromatic α-carbon activation and hydrogen transfer mechanisms - Guang-Hui Liu; Wen-Ao Shi; Jun Li; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Jie Kang; Chen Shi; Xian-Yong Wei (Fuel, 2024)

Development of porous materials via protein/polysaccharides/polyphenols nanoparticles stabilized Pickering high internal phase emulsions for adsorption of Pb2+ and Cu2+ ions - Cheng Wang; Mian Wei; Huipeng Zhu; Lu Wang; Song Ni; Xiaoyu Li; Dawei Gao (Food Chemistry, 2024)

Rethinking high-resolution remote sensing image segmentation not limited to technology: a review of segmentation methods and outlook on technical interpretability - Qianpeng Chong; Mengying Ni; Jianjun Huang; Guangyi Wei; Ziyi Li; Jindong Xu (International Journal of Remote Sensing, 2024)

Memory Trace for Fear Extinction: Fragile yet Reinforceable - Ying Liu; Shuai Ye; Xin-Ni Li; Wei-Guang Li (Neuroscience Bulletin, 2024)
Fear extinction is a biological process in which learned fear behavior diminishes without anticipated reinforcement, allowing the organism to re-adapt to ever-changing situations. Based on the behavioral hypothesis that extinction is new learning and forms an extinction memory, this new memory is more readily forgettable than the original fear memory. The brain’s cellular and synaptic traces underpinning this inherently fragile yet reinforceable extinction memory remain unclear. Intriguing questions are about the whereabouts of the engram neurons that emerged during extinction learning and how they constitute a dynamically evolving functional construct that works in concert to store and express the extinction memory. In this review, we discuss recent advances in the engram circuits and their neural connectivity plasticity for fear extinction, aiming to establish a conceptual framework for understanding the dynamic competition between fear and extinction memories in adaptive control of conditioned fear responses.

Environmental DNA metabarcoding reveals fish diversity, community assembly and one invasive species prevalence in a National Park of Liaohe in September - Ni Xin; Zhao Li; Yong-Wei Jiang; Hui Wang; Juan Tan; Yang Li; Bing-Jiao Sun; Xiao-Long Lin (Frontiers in Marine Science, 2024)
The escalating environmental changes are imposing multiple pressures on biodiversity conservation, thereby, more attention has been paid to fish diversity and community assembly patterns. Fish diversity in Liaohe River has deteriorated significantly due to overfishing, environmental pollution and other reasons, in addition, no fish survey related research has been published in Liaohe National Park in recent years. In order to study the diversity of fish species in the area and to investigate the presence of any invasive species. This study used eDNA metabarcoding to explore the distribution and diversity of fish communities in the Liaohe National Park. The study showed that a total of 54 species of fish from six orders, 14 families, and 39 genera were detected, meantime, the invasive species Lepomis cyanellus was found at two sampling sites. The α-diversity results showed that estuarine sites had the highest species diversity. The spatial structure of fish communities in the upstream and downstream reaches were similar as indicated by non-metric multidimensional scaling. In our study, the fish community is influenced by both deterministic and stochastic processes, with the stochastic processes being the main factor. The potential existence of L. cyanellus in Liaohe National Park might be resulted from aquaculture, ornamental pet trade, other economic fish farming, artificial release. The relatively low number of fish species in this study may be attributed to the limited number of sampling events and sampling sites. In addition to these factors, over exploitation of resources, water pollution, and the invasion of alien species have directly impacted the biodiversity of aquatic life. The results of this study lay a foundation for the future biodiversity investigation in National Parks of China, meantime, the use of eDNA monitoring is crucial to prevent, to control and limit the spreading of invasive species in advance.

Iron-containing nanominerals for sustainable phosphate management: A comprehensive review and future perspectives - Teng Bao; Mekdimu Mezemir Damtie; Chu Yan Wang; Cheng Long Li; Zhijie Chen; Kuk CHO; Wei Wei; Peng Yuan; Ray L. Frost; Bing-Jie Ni (Science of The Total Environment, 2024)

Efficacy of the SDGSAT-1 glimmer imagery in measuring sustainable development goal indicators 7.1.1, 11.5.2, and target 7.3 - Shaoyang Liu; Congxiao Wang; Zuoqi Chen; Wei Li; Lingxian Zhang; Bin Wu; Yan Huang; Yangguang Li; Jingwen Ni; Jianping Wu; Bailang Yu (Remote Sensing of Environment, 2024)

Subtypes of Blastocystis in Tibetan Antelope (Pantholops hodgsonii) - Wei-Lan Yan; Xiao-Man Li; Si-Yuan Qin; Nian-Yu Xue; Yang Zou; Jing-Hao Li; Xiao-Xuan Zhang; Hong-Bo Ni (Research in Veterinary Science, 2024)

Enrichment process, structural prediction, isolation, in vitro cytotoxic and anti-inflammatory effects of triterpenoid saponins in Camellia japonica L. leaves water extract through UPLC-Q-TOF based mass spectrometry similarity networking - Hui Liu; Lisha Bi; Qirun Chen; Xiaozhi He; Huan Yan; Wei Ni; Wenjuan Wu; Li He; Haiyang Liu (Food Chemistry, 2024)

A review of solid wastes-based stabilizers for remediating heavy metals co-contaminated soil: Applications and challenges - Yuliang Zhang; Pingfeng Fu; Wen Ni; Siqi Zhang; Sheng Li; Wei Deng; Wentao Hu; Jia Li; Fuyun Pei; Linfeng Du; Yueling Wang (Science of The Total Environment, 2024)

Rapid nitrite accumulation and sludge granulation in low-C/N nitrate industrial wastewater: Specific strategies and proposed sludge transformation mechanisms - Lifang Liu; Wei-Kang Qi; Li Zhang; Shu-Jun Zhang; Shou-Qing Ni; Yongzhen Peng; Cong Wang (Journal of Water Process Engineering, 2024)

Complexation between butyl xanthate and Cu enhanced peroxydisulfate activation and cation redox cycle by Fe-Cu-LDH/biochar - Baoxin Li; Xinjiang Hu; Yanling Gu; Wei Zhang; Weihua Xu; Hailan Yang; Shujing Ye; Zhongzhu Yang; Ni Liu; Xiaofei Tan (Journal of Environmental Chemical Engineering, 2024)

Windows of sensitivity for risk of adverse birth outcomes related to gestational PM2.5 exposure: Evidence from a natural experiment - Wei Ni; Yuhan Xing; Guoju Li; Zhanhui Du; Ping Yang; Qinzheng Wang; Xinmeng Yang; Bei Lyu; Hongge Fa; Qiuling Shi; Quansheng Xing (Environmental Pollution, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

Long Non-Coding RNA MALAT1 Protects Against Spinal Cord Injury via Suppressing microRNA-125b-5p Mediated Microglial M1 Polarization, Neuroinflammation, and Neural Apoptosis - Yuanlong Li; Hua Fan; Xiong Han; Jun Sun; Ming Ni; Xiaodan Hou; Fengqin Fang; Wei Zhang; Peizhi Ma (Molecular Neurobiology, 2024)

Enhanced split-type photoelectrochemical aptasensor incorporating a robust antifouling coating derived from four-armed polyethylene glycol - Hao Wang; Wei Li; Pengcheng Ni; Gao-Chao Fan; Xiliang Luo (Analytica Chimica Acta, 2024)

Recovery of alkali in Gracilaria agar production by electrodialysis and membrane concentration - Shanyu Xie; Shuai Zhong; Juan Wang; Jinfang Chen; Lijun Li; Xiping Du; Tao Hong; Mingjing Zheng; Yanbing Zhu; Wei Yin; Qingbiao Li; Hui Ni; et al. (Algal Research, 2024)

Nanoplastic propels diet-induced NAFL to NASH via ER-mitochondrial tether-controlled redox switch - Jie Wei; Jintao Liu; Huan Wang; Kai Wen; Xiuye Ni; Yilong Lin; Jingru Huang; Xiang You; Zhao Lei; Juan Li; Heqing Shen; Yi Lin (Journal of Hazardous Materials, 2024)

Efficient degradation of imidacloprid by surface discharge cold plasma: Mechanism of interaction between ROS and molecular structure and evaluation of residual toxicity - Jia-Bao Ni; Xiao-Fang Jia; Jun-Ying Zhang; Chang-Jiang Ding; Wen-Li Tian; Wen-Jun Peng; Sara Zielinska; Hong-Wei Xiao; Xiao-Ming Fang (Journal of Hazardous Materials, 2024)

Post-cumulus control on copper isotopic fractionation during oceanic intra-crustal magmatic differentiation - Wei-Qi Zhang; Chuan-Zhou Liu; C. Johan Lissenberg; Xiao-Ni Li (Geochimica et Cosmochimica Acta, 2024)

Unveiling the aromatic intricacies of Wuyi Rock Tea: A comparative study on sensory attributes and odor-active compounds of Rougui and Shuixian varieties - Daoliang Wang; Zhibin Liu; Xiaoye Lan; Cainan Wang; Wensong Chen; Sijia Zhan; Yaqian Sun; Weiying Su; Chih-Cheng Lin; Wei Liu; Yuan Liu; Li Ni (Food Chemistry, 2024)

Modeling of forced-vibration systems using continuous-time state-space neural network - Hong-Wei Li; Yi-Qing Ni; You-Wu Wang; Zheng-Wei Chen; En-Ze Rui; Zhao-Dong Xu (Engineering Structures, 2024)

Study on indoor thermal perception, behavioral adaptation in late pregnancy and their effects on adverse birth outcomes in south China - Jie Ni; Huailin Wang; Xinyue Yu; Run Gao; Yanqiu Li; Zhaosong Fang; Jason Kai Wei Lee; Zhenghong Zhu; Maimaitiminjiang Wulayin; Xin Chen; Cunrui Huang; Qiong Wang (Building and Environment, 2024)

CsBZR1 Family Transcription Factors in Wild and Cultural Tea Plants and Their Response to Hormone and Abiotic Stress - Jing-Wen Li; Ping Zhou; Ni Yang; Zhi-Hang Hu; Yi Chen; Wei Luo; Jie-Yu Kong; Zhi-Yuan Qin; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Growth Regulation, 2024)

Unveiling the spatiotemporal evolutionary patterns of eriophyoid mites in China - Ni Li; Yue Hu; Liang‐Fei Yao; Wei‐Nan Gao; Xiao‐Feng Xue (Zoologica Scripta, 2024)
Eriophyoid mites are among the most species‐rich superfamilies (Eriophyoidea) in the Acari, consisting of over 5000 named species. Although they exhibit a geographically uneven worldwide distribution, their regional spatiotemporal evolutionary patterns remain largely unknown. Here, we compiled a data set including 3058 occurrence records assigned into 1203 species in China. We found that eriophyoid mite species richness is higher in the southeast and lower in the northwest of China, coinciding with the 500‐mm annual precipitation isoline. Using fragments of two mitochondrial genes ( COI , 12S rRNA) and two nuclear genes ( 18S rRNA, 28S rRNA) of 304 eriophyoid mite species, we constructed a regional dated phylogenetic tree in China. Our spatiotemporal analysis revealed that mountains in eastern and southern China had high eriophyoid mite species richness and phylogenetic clustering, possessing both ancient and young mite lineages. Species distribution modelling (SDM) results showed that the predicted suitable area of eriophyoid mites slightly expanded from the last inter‐glacial period to the last glacial maximum period. In comparison with the current SDM, a significantly larger distribution range was observed in future scenarios. These findings suggest that mountains in eastern and southern China acted as not only cradles—recent rapid speciation, but also museums—centre of gradual accumulation and preservation and provide insights into monitoring and conserving eriophyoid mites.

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Performance of aerobic denitrifying fungal community for promoting nitrogen reduction and its application in drinking water reservoirs - Tao Liu; Ziying Zhao; Haiyun Li; Mukesh Kumar Awasthi; Dmitry B. Kosolapov; Tongchao Ni; Ben Ma; Xiaoyan Liu; Xiang Liu; Wei Zhi; Haihan Zhang (Journal of Environmental Management, 2024)

27-Hydroxycholesterol activates the GSK-3β/β-catenin signaling pathway resulting in intestinal fibrosis by inducing oxidative stress: effect of dietary interventions - Wei Xiao; Chunyan Hu; Yifan Ni; Jie Wang; Kailin Jiao; Ming Zhou; Zhong Li (Inflammation Research, 2024)

Performance of the Aspergillus galactomannan lateral flow assay with a digital reader for the diagnosis of invasive aspergillosis: a multicenter study - Jian Guo; Chenlu Xiao; Wenjie Tian; Li Lv; Liang Hu; Lijun Ni; Dongjiang Wang; Wei Li; Dan Qiao; Wenjuan Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The objective of this multicenter study was to compare the diagnostic performance of lateral flow assay (LFA) and enzyme-linked immunosorbent assay (ELISA) to detect the Dynamiker Aspergillus Galactomannan levels in serum and bronchoalveolar lavage fluid (BALF) samples for I. Methods We registered 310 clinically suspected Aspergillus infection patients from December 2021 to February 2023 and classified them into subgroups as the “IA group” and “non-IA group” based on the latest EORTC/MSG guidelines. The immunoassays were analyzed by LFA and ELISA respectively. Results Galactomannan was examined using LFA, and serum and BALF samples demonstrated sensitivities of 82.57% and 89.47%, specificities of 90.76% and 92.00%, PPVs of 89.11% and 96.23%, and NPVs of 85.04% and 79.31%, respectively. Galactomannan was observed using two assays in serum and BALF samples and showed PPAs of 95.11% and 93.33%, NPAs of 89.19% and 96.30%, and TPAs of 92.47% and 94.25%, respectively. The ROC curve demonstrated that LFA had optimum diagnostic value when the index value ( I value) = 0.5, the sensitivity was 84.94%, and the specificity was 90.97%. Conclusion Compared to the ELISA method, the LFA has shown excellent performance for the diagnosis of IA in serum and BALF sample and can be used as an assay for the early diagnosis of patients with IA. The dynamic change in galactomannan levels may be useful for assessing treatment response.

Hydrogeochemistry and indicators of flowback and produced water from wells that are hydraulically fractured with recycled wastewater: A case study of the Changning gas field in the Sichuan Basin - Dan Liu; Wei Xiong; Xiaowei Zhang; Wei Guo; Wanting Li; Jinliang Gao; Lixia Kang; Yuyang Liu; Zhaoyuan Shao; Lin Zhang; Cong Yu; Fengrong Liao; et al. (Applied Geochemistry, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

IVIVE-PBPK based new approach methodology for addressing early life toxicity induced by Bisphenol A - Mengmei Ni; Deepika Deepika; Xiaomeng Li; Wei Xiong; Lishi Zhang; Jinyao Chen; Vikas Kumar (Environmental Research, 2024)

Fulvic acid improves the degradation performance of Fe-Mn bimetallic in peroxymonosulfate based advanced oxidation process - Jieyi Wang; Mengke Li; Hairong Shen; Chenquan Ni; Hui Zhong; Wei Sun; Mingqiang Ye; Yetao Tang; Zhiguo He (Chemical Engineering Journal, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Frontostriatal circuitry and the tryptophan kynurenine pathway in major psychiatric disorders - Sugai Liang; Liansheng Zhao; Peiyan Ni; Qiang Wang; Wanjun Guo; Yan Xu; Jia Cai; Shiwan Tao; Xiaojing Li; Wei Deng; Lena Palaniyappan; Tao Li (Psychopharmacology, 2024)

How the experience of California wildfires shape Twitter climate change framings - Jessie W. Y. Ko; Shengquan Ni; Alexander Taylor; Xiusi Chen; Yicong Huang; Avinash Kumar; Sadeem Alsudais; Zuozhi Wang; Xiaozhen Liu; Wei Wang; Chen Li; Suellen Hopfer (Climatic Change, 2024)
Climate communication scientists search for effective message strategies to engage the ambivalent public in support of climate advocacy. The personal experience of wildfire is expected to render climate change impacts more concretely, pointing to a potential message strategy to engage the public. This study examined Twitter discourse related to climate change during the onset of 20 wildfires in California between the years 2017 and 2021. In this mixed method study, we analyzed tweets geographically and temporally proximal to the occurrence of wildfires to discover framings and examined how frequencies in climate framings changed before and after fires. Results identified three predominant climate framings: linking wildfire to climate change, suggesting climate actions, and attributing climate change to adversities besides wildfires. Mean tweet frequencies linking wildfire to climate change and attributing adversities increased significantly after the onset of fire. While suggesting climate action tweets also increased, the increase was not statistically significant. Temporal analysis of tweet frequencies for the three themes of tweets showed that discussion increased after the onset of a fire but persisted typically no more than 2 weeks. For fires that burned for longer periods of more than a month, external events triggered climate discussions. Our findings contribute to identifying how the personal experience of wildfire shapes Twitter discussion related to climate change, and how these framings change over time during wildfire events, leading to insights into critical time points after wildfire for implementing message strategies to increase public engagement on climate change impacts and policy.

Pyroptosis induction synergized with IDO inhibition of ternary biomedicine for photodynamic activated tumor immunotherapy - Ali Chen; Ni Yang; Wei Zhang; Rongrong Zheng; Rui Yu; Renjing Kong; Yuqing Wang; Hong Cheng; Xiyong Yu; Shiying Li (Chemical Engineering Journal, 2023)

Design of chlorella-inspired and smart-responsive bio-microspheres and their application in eco-friendly anti-biofouling coatings - Xingxing Ni; Chenxi Li; Jianlin Zhou; Mingting Zhang; Bo You; Limin Wu; Wei Li; Jie Guo (Chemical Engineering Journal, 2023)

An epi-allele of SMS causes Sanming dominant genic male sterility in rice - Yachun Yang; Cheng Zhang; Hao Li; Zeyuan Yang; Zuntao Xu; Dewei Tai; Dahu Ni; Pengcheng Wei; Chengxin Yi; Jianbo Yang; Yong Ding (Science China Life Sciences, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Dust diffusion laws during partition excavation by boom-type roadheader in a metro tunnel - Ning Liu; Xiong Wu; E Deng; Yi-Qing Ni; Wei-Chao Yang; Guo-Zhi Li (Tunnelling and Underground Space Technology, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Effect of electrohydrodynamic drying on bee pollen biochemical pathways - Jia-Bao Ni; Yin-Chen Wang; Hong-Wei Xiao; Sara Zielinska; Wen-Li Tian; Xiang-Xin Li; Wen-Jun Peng; Xiao-Ming Fang (Journal of Cleaner Production, 2023)

Synergistic transfer of active hydrogen in the catalytic hydroconversion of lignite-derived aryl ethers to cyclanes: A combined experimental and DFT study - Guang-Hui Liu; Yong-Chao Qi; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Zhan-Ku Li; Xian-Yong Wei (Fuel, 2023)

Integration of hyperspectral imaging, non-targeted metabolomics and machine learning for vigour prediction of naturally and accelerated aged sweetcorn seeds - Tingting Zhang; Long Lu; Ni Yang; Ian D. Fisk; Wensong Wei; Li Wang; Jing Li; Qun Sun; Rensen Zeng (Food Control, 2023)

Transportation of fine particles controlled by particles flocculation is a key feature of soil erosion on gentle slope land - Jiangwen Li; Banglin Luo; Xihao Wei; En Ci; Jiupai Ni; Chaofu Wei; Shouqin Zhong (CATENA, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Climatic variability during the 4.2 ka event: Evidence from a high-resolution pollen record in southeastern China - Haoyan Wang; Kai Li; Mengna Liao; Wei Ye; Yun Zhang; Jian Ni (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Reducing uncertainties in hydromechanical modeling with a recently developed Rosetta 3 podeotransfer function - Wei Shao; Sijie Chen; Meijun Li; Ye Su; Junjun Ni; Jianzhi Dong; Yonggen Zhang; Zongji Yang (Engineering Geology, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

OsGSTU5 and OsGSTU37 encoding glutathione reductases are required for cadmium tolerance in rice - Y. Yang; J. Li; H. Li; Y. Ding; W. Wu; R. Qin; J. Ni; R. Xu; P. Wei; J. Yang (International Journal of Environmental Science and Technology, 2023)

Functionalized carbon nanotube field-effect transistor biosensor for highly sensitive detection of exosomal protein - Tingxian Li; Lina Tang; Kun Li; Binzhu Liu; Meng-Meng Xiao; Nian Liu; Wei Ni; Yutao Li; Zhiyong Zhang; Guo-Jun Zhang (Analytica Chimica Acta, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Buffering capacity of submerged macrophytes against nutrient pulses increase with its coverage in shallow lakes - Chaochao Lv; Yuqing Tian; Liangliang Huang; Hang Shan; Qingchuan Chou; Wei Zhang; Haojie Su; Kuanyi Li; Xiaolin Zhang; Leyi Ni; Te Cao; Erik Jeppesen (Chemosphere, 2023)

Animal production predominantly contributes to antibiotic profiles in the Yangtze River - Jingrun Hu; Si Li; Wei Zhang; Damian E. Helbling; Nan Xu; Weiling Sun; Jinren Ni (Water Research, 2023)

The Changjiang River plume shifts from carbon source to sink when net community production exceeds a threshold in early autumn - Di Wu; Jianfang Chen; Kui Wang; Xiaobo Ni; Dewang Li; Dingyong Zeng; Wei Fan; Dawei Xu (Science of The Total Environment, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Post-harvest ripening affects drying behavior, antioxidant capacity and flavor release of peach via alteration of cell wall polysaccharides content and nanostructures, water distribution and status - Jia-Bao Ni; Magdalena Zielinska; Jun Wang; Xiao-Ming Fang; Parag Prakash Sutar; Suo-Bin Li; Xiang-Xin Li; Hui Wang; Hong-Wei Xiao (Food Research International, 2023)

Influence of interfacial properties/structure on oxygen diffusion in oil-in-water emulsions - Yanlei Li; Fangfang Chen; Zhiming Gao; Wei Xiang; Yuehan Wu; Bing Hu; Xuewen Ni; Katsuyoshi Nishinari; Yapeng Fang (Food Research International, 2023)

Evolutionary research trend of Polygonatum species: a comprehensive account of their transformation from traditional medicines to functional foods - Xiao-Li Li; Run-Hui Ma; Fan Zhang; Zhi-Jing Ni; Kiran Thakur; Shaoyun Wang; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Saikosaponin D exerts cytotoxicity on human endometrial cancer ishikawa cells by inducing apoptosis and inhibiting metastasis through MAPK pathways - Tong-Tong Tang; Li Jiang; Qian Zhong; Zhi-Jing Ni; Kiran Thakur; Mohammad Rizwan Khan; Zhao-Jun Wei (Food and Chemical Toxicology, 2023)

Deposition of a newly identified Mesoproterozoic iron formation from the Dabie orogen: Influenced by high-T hydrothermal fluid and redox stratification - Jun Hu; Wei Jin; Yang Tian; Xin Deng; Sanzhong Li; Lingyao Kong; M. Santosh; Yongjiang Liu; Jing Wang; Daliang Xu; Ni Peng (Precambrian Research, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Crustal accretion in a slow-spreading center of Meso-Tethyan Ocean: Constraints from cumulates in the Dongco ophiolite (Central Tibet) - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Zhen Zhang; Yin-Zheng Lin; Chuan-Zhou Liu (Lithos, 2023)

Low-rate ferrate dosing damages the microbial biofilm structure through humic substances destruction and facilitates the sewer biofilm control - Xiaofang Yan; Jing Sun; Yizhen Wang; Zisha Zhang; Chuning Zhang; Wei Li; Juan Xu; Xiaohu Dai; Bing-Jie Ni (Water Research, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Tailoring valence state of V in V-Mo atomically dispersed ensemble enables exceptional NH4HSO4 poisoning resistance for NH3-SCR reaction - Zhiwei Huang; Sufeng Guo; Wen Chen; Meirong Huang; Jiangwei Ni; Qiqi Zhou; Mingshuo Tian; Xiaomin Wu; Huawang Zhao; Huazhen Shen; Wei Li; Guohua Jing (Chemical Engineering Journal, 2023)

Stochastic-based approach to quantify the uncertainty of groundwater vulnerability - Chuen-Fa Ni; Tien-Duc Vu; Wei-Ci Li; Minh-Tuan Tran; Van-Cuong Bui; Minh-Hoang Truong (Stochastic Environmental Research and Risk Assessment, 2023)

Immunomodulatory and Anti-inflammatory effect of Neural Stem/Progenitor Cells in the Central Nervous System - Wei Ni; Murugan Ramalingam; Yumeng Li; Jeong-Hui Park; Khandmaa Dashnyam; Jung-Hwan Lee; Nora Bloise; Lorenzo Fassina; Livia Visai; Maria Gabriella Cusella De Angelis; Jose Luis Pedraz; Hae-Won Kim; et al. (Stem Cell Reviews and Reports, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

CO2-induced reconstruction for ORR-enhanced solid oxide fuel cell cathode - Yuan Zhang; Junbiao Li; Heping Xie; Zhipeng Liu; Suling Shen; Ying Teng; Daqin Guan; Shuo Zhai; Yufei Song; Wei Zhou; Bin Chen; Meng Ni; et al. (Chemical Engineering Journal, 2023)

High-efficient removal of ammonium and co-production of protein-rich biomass from ultrahigh-NH4+ industrial wastewater by mixotrophic Galdieria sulphuraria - Baojun Zhu; Yali Zheng; Hao Shen; Dong Wei; Li Ni; Guoyou Wei (Algal Research, 2023)

Land use and hydrological factors control concentrations and diffusive fluxes of riverine dissolved carbon dioxide and methane in low-order streams - Wei Tang; Y. Jun Xu; Maofei Ni; Siyue Li (Water Research, 2023)

Direct measurements and CFD simulations on ice-induced hull pressure of a ship in floe ice fields - Kai Zhong; Bao-Yu Ni; Zhiyuan Li; Xuesong Xu; Hongyu Wei; Hongyuan Li; Yanzhuo Xue (Ocean Engineering, 2023)

Compositional changes of CH, O, and N moieties in petroleum ether-extractable portions from the three-step mild degradation of Dongming lignite - Yan-Jun Li; Wei Zhao; Guang-Hui Liu; Hao-Dong An; Ya-Jun Ma; Yu-Hong Kang; Yong Gao; Ni Bai; Ding-Kai Wang; Xian-Yong Wei; Hong-Cun Bai (Fuel, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Anammox upflow hybrid reactor: Nitrogen removal performance and potential for phosphorus recovery - Ying Song; Jialing Ni; Yan Guo; Kengo Kubota; Wei-Kang Qi; Yu-You Li (Chemosphere, 2023)

A review of global bedrock (234U/238U) disequilibrium and its controlling factors on earth's surface - Nicholas Chia Wei Ng; Chao Li; Chenyu Wang; Yulong Guo; Zhifei Duan; Ni Su; Shouye Yang (Journal of Geochemical Exploration, 2023)

Comparison of potent odorants in raw and cooked mildly salted large yellow croaker using odor-active value calculation and omission test: Understanding the role of cooking method - Haocheng Wei; Yukun Wei; Xujian Qiu; Shen Yang; Feng Chen; Hui Ni; Qingbiao Li (Food Chemistry, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

Effects of aging on the persistence of cadmium adsorption on organic fertilizers - Y. Wang; Q. Zhao; Z. Wei; J. Li; W. Ni; Z. Wu; W. Wu; T. Zhou; P. Christie (International Journal of Environmental Science and Technology, 2023)

Bedrock (234U/238U) disequilibrium and its impact on inferring sediment comminution age in Taiwan Island - Nicholas Chia Wei Ng; Chao Li; Chenyu Wang; Yulong Guo; Zhifei Duan; Ni Su; Shouye Yang (Applied Geochemistry, 2023)

Specific PhytOC fractions in rice straw and consequent implications for potential of phytolith carbon sequestration in global paddy fields - Xiaomin Yang; Zhaoliang Song; Laodong Guo; Jingxu Wang; Yilun Ni; Zimin Li; Qian Hao; Qiang Li; Lele Wu; Wei Kuang; Yang Liu; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Puerol and pueroside derivatives from Pueraria lobata and their anti-inflammatory activity - Ying-Jie Sun; Shi-Jie Cao; Feng-Ni Liang; Jin-Yan Li; Xiang-Yu Zhang; Wei Li; Li-Qin Ding; Feng Qiu (Phytochemistry, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

Petrogenesis of late Cenozoic high Mg andesites with high Nb/Ta ratios in Northern Songliao Basin, NE China - Yong-wei Zhao; Haibo Zou; Ni Li (Lithos, 2023)

Reduction of miR-133a-3p contributes to apoptosis and gasdermin E-mediated pyroptosis of keratinocytes in skin exposed to ultraviolet B radiation - Changjun Song; Wenlan Zhang; Ta Xiao; Min Li; Yiqun Zhang; Xuecui Wei; Yujie Chen; Ni Lian; Yangying Ke; Hui Yu; Min Li; Heng Gu; et al. (Journal of Photochemistry and Photobiology B: Biology, 2023)

Sex-specific thyroid disruption caused by phenanthrene in adult zebrafish (Danio rerio) - Liqiao Zhong; Luyin Wu; Huijun Ru; Nian Wei; Fan Yao; He Zhang; Zhaohui Ni; Xinbin Duan; Yunfeng Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Lattice doping of Zn boosts oxygen vacancies in Co3O4 Nanocages: Improving persulfate activation via forming Surface-Activated complex - Mei-Mei Wang; Li-Juan Liu; Jia-Rui Xi; Ying Ding; Peng-Xi Liu; Liang Mao; Bing-Jie Ni; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Roles of PKAc1 and CRE1 in cellulose degradation, conidiation, and yellow pigment synthesis in Trichoderma reesei QM6a - Ni Li; Yumeng Chen; Yaling Shen; Wei Wang (Biotechnology Letters, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Multi-stage melt impregnation and magma–seawater interaction in a slow-spreading oceanic lithosphere: constraints from cumulates in the Lagkorco ophiolite (central Tibet) - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Zhen-Yu Zhang; Xiao-Ni Li; Zhen Zhang; Yin-Zheng Lin (Contributions to Mineralogy and Petrology, 2022)

Numerical Simulation of an Air-Bubble System for Ice Resistance Reduction - Bao-Yu Ni; Hongyu Wei; Zhiyuan Li; Bin Fang; Yanzhuo Xue (Journal of Marine Science and Engineering, 2022)
Ships sailing through cold regions frequently encounter floe ice fields. An air-bubble system that reduces friction between the hull and ice floes is thus considered useful for the reduction of ice-induced resistance. In this study, a numerical analysis procedure based on coupled finite volume method (FVM) and discrete element method (DEM) is proposed to simulate complicated hull-water-gas-ice interactions for ice-going ships installed with air-bubble systems. The simulations reveal that after turning on the air-bubble system ice floes in contact with the hull side wall are pushed away from the hull by the gas-water mixture, resulting in an ice-free zone close to the side hull. It is found that the drag reduction rate increases with the increase of ventilation, while the bow ventilation plays a deciding role in the overall ice-resistance reduction. The proposed procedure is expected to facilitate design of new generations of ice-going ships.

Downregulation of CRTC1 Is Involved in CUMS-Induced Depression-Like Behavior in the Hippocampus and Its RNA Sequencing Analysis - Dezhu Li; Qi Liao; Yang Tao; Saiqi Ni; Chuang Wang; Dingli Xu; Dongsheng Zhou; Xingxing Li; Xinchun Jin; Xiaowei Chen; Wei Cui; Junfang Zhang (Molecular Neurobiology, 2022)

Construction and comprehensive analysis of a lncRNA–mRNA interactive network to reveal a potential lncRNA for hepatic encephalopathy development - Chihao Zhang; Wei Ni; Yiming Zhu; Jiayun Lin; Hongjie Li; Zhifeng Zhao; Ke Wang; Haizhong Huo; Meng Luo (Human Cell, 2022)

Hippocampal Activated Microglia May Contribute to Blood–Brain Barrier Impairment and Cognitive Dysfunction in Post-Traumatic Stress Disorder-Like Rats - Kun Ni; Jixiang Zhu; Xuan Xu; Yue Liu; Shuai Yang; Yulin Huang; Rui Xu; Li Jiang; Juan Zhang; Wei Zhang; Zhengliang Ma (Journal of Molecular Neuroscience, 2022)

Spectral clustering with anchor graph based on set-to-set distances for large-scale hyperspectral images - Yao Qin; Sinong Quan; Chongyang Wei; Weiping Ni; Kun Li; Xiaohu Dong; Yuanxin Ye (International Journal of Remote Sensing, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

Schwann-like cell conditioned medium promotes angiogenesis and nerve regeneration - Jiahong Yu; Kai Ye; Jing Li; Yusheng Wei; Jiqin Zhou; Wei Ni; Lei Zhang; Tianyan Chen; Bin Tang; Hong Xu; Jiabo Hu (Cell and Tissue Banking, 2022)

The Key Regulator of Necroptosis, RIP1 Kinase, Contributes to the Formation of Astrogliosis and Glial Scar in Ischemic Stroke - Yong-Ming Zhu; Liang Lin; Chao Wei; Yi Guo; Yuan Qin; Zhong-Sheng Li; Thomas A. Kent; Claire E. McCoy; Zhan-Xiang Wang; Yong Ni; Xian-Yong Zhou; Hui-Ling Zhang (Translational Stroke Research, 2021)
Necroptosis initiation relies on the receptor-interacting protein 1 kinase (RIP1K). We recently reported that genetic and pharmacological inhibition of RIP1K produces protection against ischemic stroke-induced astrocytic injury. However, the role of RIP1K in ischemic stroke-induced formation of astrogliosis and glial scar remains unknown. Here, in a transient middle cerebral artery occlusion (tMCAO) rat model and an oxygen and glucose deprivation and reoxygenation (OGD/Re)-induced astrocytic injury model, we show that RIP1K was significantly elevated in the reactive astrocytes. Knockdown of RIP1K or delayed administration of RIP1K inhibitor Nec-1 down-regulated the glial scar markers, improved ischemic stroke-induced necrotic morphology and neurologic deficits, and reduced the volume of brain atrophy. Moreover, knockdown of RIP1K attenuated astrocytic cell death and proliferation and promoted neuronal axonal generation in a neuron and astrocyte co-culture system. Both vascular endothelial growth factor D (VEGF-D) and its receptor VEGFR-3 were elevated in the reactive astrocytes; simultaneously, VEGF-D was increased in the medium of astrocytes exposed to OGD/Re. Knockdown of RIP1K down-regulated VEGF-D gene and protein levels in the reactive astrocytes. Treatment with 400 ng/ml recombinant VEGF-D induced the formation of glial scar; conversely, the inhibitor of VEGFR-3 suppressed OGD/Re-induced glial scar formation. RIP3K and MLKL may be involved in glial scar formation. Taken together, these results suggest that RIP1K participates in the formation of astrogliosis and glial scar via impairment of normal astrocyte responses and enhancing the astrocytic VEGF-D/VEGFR-3 signaling pathways. Inhibition of RIP1K promotes the brain functional recovery partially via suppressing the formation of astrogliosis and glial scar. Graphical Abstract

Overexpression of an aquaporin protein from Aspergillus glaucus confers salt tolerance in transgenic soybean - Feiwu Li; Hejia Ni; Wei Yan; Yanbo Xie; Xiaodan Liu; Xichang Tan; Ling Zhang; Shi-Hong Zhang (Transgenic Research, 2021)

Terpenoids-enriched fraction of Celastrus orbiculatus sensitizes gemcitabine by disrupting Chk1/RAD51-mediated DNA damage response in pancreatic cancer - Yang Zhao; Zhuangzhuang Jiang; Tengyang Ni; Wei Jiang; Kehui Zhou; Yuping Liu; Yanqing Liu; Li Tao (Genome Instability & Disease, 2021)

Linking circular intronic RNA degradation and function in transcription by RNase H1 - Xiang Li; Jia-Lin Zhang; Yun-Ni Lei; Xiao-Qi Liu; Wei Xue; Yang Zhang; Fan Nan; Xiang Gao; Jun Zhang; Jia Wei; Li Yang; Ling-Ling Chen (Science China Life Sciences, 2021)

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

The Amygdala Responds Rapidly to Flashes Linked to Direct Retinal Innervation: A Flash-evoked Potential Study Across Cortical and Subcortical Visual Pathways - Yanmei Chen; Yiling Ni; Jianhong Zhou; Hua Zhou; Qian Zhong; Xinyue Li; Jichuan Zhang; Yuanye Ma; Jingkuan Wei (Neuroscience Bulletin, 2021)

In vitro and In vivo Antibacterial Effects of Nisin Against Streptococcus suis - Haodan Zhu; Lixiao Han; Yanxiu Ni; Zhengyu Yu; Dandan Wang; Junming Zhou; Bin Li; Wei Zhang; Kongwang He (Probiotics and Antimicrobial Proteins, 2021)

Toxicity Changes of Heavily Polluted River Sediments on Daphnia magna Before and After Dredging - Li-Ling Zhang; Zhou-Tao Pei; Ya-Ni Zhao; Jing Zhang; Rou-Rou Xu; Meng Zhang; Wen-Qiang Wang; Li-Wei Sun; Guang-Can Zhu (Bulletin of Environmental Contamination and Toxicology, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Seasonal and spatial variability in surface p CO 2 and air–water CO 2 flux in the Chesapeake Bay - Baoshan Chen; Wei‐Jun Cai; Jean R. Brodeur; Najid Hussain; Jeremy M. Testa; Wenfei Ni; Qian Li (Limnology and Oceanography, 2020)
Interactions between riverine inputs, internal cycling, and oceanic exchange result in dynamic variations in the partial pressure of carbon dioxide ( p CO 2 ) in large estuaries. Here, we report the first bay‐wide, annual‐scale observations of surface p CO 2 and air–water CO 2 flux along the main stem of the Chesapeake Bay, revealing large annual variations in p CO 2 (43–3408 μ atm) and a spatial‐dependence of p CO 2 on internal and external drivers. The low salinity upper bay was a net source of CO 2 to the atmosphere (31.2 mmol m −2 d −1 ) supported by inputs of CO 2 ‐rich Susquehanna River water and the respiration of allochthonous organic matter, but part of this region was also characterized by low p CO 2 during spring and fall phytoplankton blooms. p CO 2 decreased downstream due to CO 2 ventilation supported by long water residence times, stratification, mixing with low p CO 2 water masses, and carbon removal by biological uptake. The mesohaline middle bay was a net CO 2 sink (−5.8 mmol m −2 d −1 ) and the polyhaline lower bay was nearly in equilibrium with the atmosphere (1.0 mmol m −2 d −1 ). Although the main stem of the bay was a weak CO 2 source (3.7 ± 3.3 × 10 9 mol C) during the dry hydrologic (calendar) year 2016, our observations showed higher river discharge could decrease CO 2 efflux. In contrast to many other estuaries worldwide that are strong sources of CO 2 to the atmosphere, the Chesapeake Bay and potentially other large estuaries are very weak CO 2 sources in dry years, and could even turn into a CO 2 sink in wet years.

Decreased serum albumin level indicates poor prognosis of COVID-19 patients: hepatic injury analysis from 2,623 hospitalized cases - Wei Huang; Chenze Li; Zhiquan Wang; Hong Wang; Ning Zhou; Jiangang Jiang; Li Ni; Xin A. Zhang; Dao-Wen Wang (Science China Life Sciences, 2020)

Cytotoxic triquinane-type sesquiterpenoids from the endophytic fungus Cerrena sp. A593 - Hong-Xin Liu; Hai-Bo Tan; Yu-Chan Chen; Sai-Ni Li; Hao-Hua Li; Wei-Min Zhang (Natural Product Research, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

RIG-I aggravates interstitial fibrosis via c-Myc-mediated fibroblast activation in UUO mice - Zhuanli Zhou; Jiayun Ni; Jingyao Li; Chuanbing Huo; Naijun Miao; Fan Yin; Qian Cheng; Dan Xu; Hongyan Xie; Panpan Chen; Peiqing Zheng; Yingying Zhang; et al. (Journal of Molecular Medicine, 2020)
Progressive tubulointerstitial fibrosis is the common final outcome for all kidney diseases evolving into chronic kidney disease (CKD), whereas molecular mechanisms driving fibrogenesis remain elusive. Retinoic acid-inducible gene-I (RIG-I), an intracellular pattern recognition receptor, is originally identified participating in immune response by recognizing virus RNA. Here, we revealed for the first time that RIG-I was induced in unilateral ureteral obstruction (UUO) and folic acid (FA) renal fibrosis models and moderate-degree renal fibrosis patients. Besides, we found RIG-I was mainly located in renal tubular epithelial cells and promoted the production and release of inflammatory cytokines, such as interleukin (IL)-1β and IL-6 through activation of NF-κB. Inflammatory cytokines released by tubular epithelial cells activated c-Myc-mediated TGF-β/Smad signaling in fibroblasts, which in turn aggravated interstitial fibrosis by promoting fibroblast activation and production of extracellular matrix components (ECM). Deficiency of RIG-I attenuated renal fibrosis by the regulation of inflammatory responses, c-Myc expression, and fibroblast activation. Besides, gene silencing of RIG-I reduced inflammatory cytokines in cultured tubular epithelial cells treated with Angiotensin II. Knockdown of c-Myc or c-Myc inhibitor blocked IL-1β-induced fibroblast activation. Collectively, our study demonstrates that RIG-I plays a significant role in the progress of renal fibrosis via regulating c-Myc-mediated fibroblast activation. Key messages • RIG-I was constantly elevated in kidneys from renal fibrotic mice. • RIG-I facilitated inflammatory cytokine production in tubular epithelial cells. • RIG-I aggravated renal fibrosis via c-Myc-mediated TGF-β/Smad activation.

GABAergic Abnormalities Associated with Sensorimotor Cortico-striatal Community Structural Deficits in ErbB4 Knockout Mice and First-Episode Treatment-Naïve Patients with Schizophrenia - Chengcheng Zhang; Peiyan Ni; Yikang Liu; Yang Tian; Jinxue Wei; Bo Xiang; Liansheng Zhao; Xiaojing Li; Xiaohong Ma; Wei Deng; Wanjun Guo; Rongjun Ni; et al. (Neuroscience Bulletin, 2020)

v301, a new allele of BRITTLE CULM 12, and its regulation of the early senescence of the leaf blade in rice - Ji-le Ni; Xiao-zhu Wen; Cheng-bing Tang; Wei-jiang Tian; Wen-jing Yang; Jia Xie; Xiao-bo Zhang; Yang-yang Li; Yu-zhen Xiong; Ying Sun; Zhu Zhu; Ying Wang; et al. (Acta Physiologiae Plantarum, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Interaction Between Variations in Dopamine D2 and Serotonin 2A Receptor is Associated with Short-Term Response to Antipsychotics in Schizophrenia - Liansheng Zhao; Huijuan Wang; Yamin Zhang; Jinxue Wei; Peiyan Ni; Hongyan Ren; Gang Li; Qiang Wang; Gavin P Reynolds; Weihua Yue; Wei Deng; Hao Yan; et al. (Neuroscience Bulletin, 2019)

Association analysis of polymorphism in the NR6A1 gene with the lumbar vertebrae number traits in sheep - Xiangyu Zhang; Cunyuan Li; Xiaoyue Li; Zhijin Liu; Wei Ni; Yang Cao; Yang Yao; Esenbay Islamov; Junchang Wei; Xiaoxu Hou; Shengwei Hu (Genes & Genomics, 2019)

Characterization of enzyme-immobilized catalytic support and its exploitation for the degradation of methoxychlor in simulated polluted soils - Yan Huang; Jie Li; Yuxiang Yang; Hongming Yuan; Qinmei Wei; Xiangnong Liu; Yi Zhao; Chaoying Ni (Environmental Science and Pollution Research, 2019)

The Yudomski event and subsequent decline: new evidence from δ34S data of lower and middle Cambrian evaporites in the Tarim Basin, western China - Fan-wei Meng; Zhi-li Zhang; James D. Schiffbauer; Qin-gong Zhuo; Meng-jun Zhao; Pei Ni; Wen-hang Liu; Naveed Ahsan; Saif Ur Rehman (Carbonates and Evaporites, 2019)

Responses of nitrogen concentrations and pools to multiple environmental change drivers: A meta‐analysis across terrestrial ecosystems - Kai Yue; Yan Peng; Dario A. Fornara; Koenraad Van Meerbeek; Lars Vesterdal; Wanqin Yang; Changhui Peng; Bo Tan; Wei Zhou; Zhenfeng Xu; Xiangyin Ni; Li Zhang; et al. (Global Ecology and Biogeography, 2019)
Aim We sought to understand how the individual and combined effects of multiple environmental change drivers differentially influence terrestrial nitrogen (N) concentrations and N pools and whether the interactive effects of these drivers are mainly antagonistic, synergistic or additive. Location Worldwide. Time period Contemporary. Major taxa studied Plants, soil, and soil microbes in terrestrial ecosystems. Methods We synthesized data from manipulative field studies from 758 published articles to estimate the individual, combined and interactive effects of key environmental change drivers (elevated CO 2 , warming, N addition, phosphorus addition, increased rainfall and drought) on plant, soil, and soil microbe N concentrations and pools using meta‐analyses. We assessed the influences of moderator variables on these effects through structural equation modelling. Results We found that (a) N concentrations and N pools were significantly affected by the individual and combined effects of multiple drivers, with N addition (either alone or in combination with another driver) showing the strongest positive effects; (b) the individual and combined effects of these drivers differed significantly between N concentrations and N pools in plants, but seldom in soils and microbes; (c) additive effects of driver pairs on N concentrations and pools were much more common than synergistic or antagonistic effects across plants, soils and microbes; and (d) environmental and experimental factors were important moderators of the individual, combined and interactive effects of these drivers on terrestrial N. Main conclusions Our results indicate that terrestrial N concentrations and N pools, especially those of plants, can be significantly affected by the individual and combined effects of environmental change drivers, with the interactive effects of these drivers being mostly additive. Our findings are important because they contribute to the development of models to better predict how altered N availability affects ecosystem carbon cycling under future environmental changes.

The anxiolytic effects of Bai Le Mian capsule, a traditional Chinese hypnotic in mice - Tian-Xiao Wang; Yu-Er Wu; Wei Xu; Wan-Kun Gong; Jian Ni; Wei-Min Qu; Zhi-Li Huang (Sleep and Biological Rhythms, 2019)

Stromatolites in Middle Ordovician carbonate–evaporite sequences and their carbon and sulfur isotopes stratigraphy, Ordos Basin, northwestern China - Fan-Wei Meng; Zhi-li Zhang; Xian-qin Yan; Pei Ni; Wen-Hang Liu; Fu Fan; Gu-Wei Xie (Carbonates and Evaporites, 2019)

Transcriptomic analysis of cells in response to EV71 infection and 2Apro as a trigger for apoptosis via TXNIP gene - Chenguang Yao; Kanghong Hu; Caili Xi; Ni Li; Yanhong Wei (Genes & Genomics, 2019)

Numerical assessments of recharge-dominated groundwater flow and transport in the nearshore reclamation area in western Taiwan - Chuen-Fa Ni; Wei-Ci Li; Shaohua Marko Hsu; I-Hsien Lee; Chi-Ping Lin (Environmental Monitoring and Assessment, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Identification of a novel strain, Streptomyces blastmyceticus JZB130180, and evaluation of its biocontrol efficacy against Monilinia fructicola - Mi Ni; Qiong Wu; Hong-li Wang; Wei-cheng Liu; Bin Hu; Dian-peng Zhang; Juan Zhao; De-wen Liu; Cai-ge Lu (Journal of Zhejiang University-SCIENCE B, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Neuregulin-1β modulates myogenesis in septic mouse serum-treated C2C12 myotubes in vitro through PPARγ/NF-κB signaling - Li Liu; Xueru Liu; Yiping Bai; Ni Tang; Jie Li; Yingying Zhang; Jiali Wu; Xiaobin Wang; Jicheng Wei (Molecular Biology Reports, 2018)

Contourlet-based hippocampal magnetic resonance imaging texture features for multivariant classification and prediction of Alzheimer’s disease - Ni Gao; Li-Xin Tao; Jian Huang; Feng Zhang; Xia Li; Finbarr O’Sullivan; Si-Peng Chen; Si-Jia Tian; Gehendra Mahara; Yan-Xia Luo; Qi Gao; Xiang-Tong Liu; et al. (Metabolic Brain Disease, 2018)

Secondary metabolites from the Colletotrichum gloeosporioides A12, an endophytic fungus derived from Aquilaria sinensis - Hong-Xin Liu; Hai-Bo Tan; Yu-Chan Chen; Sai-Ni Li; Hao-Hua Li; Wei-Min Zhang (Natural Product Research, 2018)

Natural variation ofCsSTOP1in tea plant (Camellia sinensis) related to aluminum tolerance - Hua Zhao; Wei Huang; Yange Zhang; Ziwei Zhang; Yong Li; Che Tang; Jie Huang; Dejiang Ni (Plant and Soil, 2018)

Identification and comparison of microRNAs in pituitary gland during prenatal and postnatal stages of sheep by deep sequencing - Xiaoyue Li; Cunyuan Li; Wei Ni; Dawei Wang; Xiaoxu Hou; Zhijin Liu; Yang Cao; Yang Yao; Xiangyu Zhang; Shengwei Hu (Journal of Genetics, 2018)

3D FEM simulation of responses of LWD multi-mode resistivity imaging sonde - Zheng-Ming Kang; Shi-Zhen Ke; Xin Li; Jin-Tai Mi; Wei-Ning Ni; Ming-Yu Li (Applied Geophysics, 2018)

Finger or Light: Stimulation Sensitivity of Visual Startle in the Coma Recovery Scale-Revised for Disorders of Consciousness - Feng Zhou; Hui Li; Kai Wang; Yanbin He; Yan Chen; Xiaoxiao Ni; Yechun Guo; Wei Lv; Jiechun Zhang; Qiuyou Xie; Ronghao Yu (Neuroscience Bulletin, 2018)

Targeted next-generation sequencing improves diagnosis of hereditary spastic paraplegia in Chinese patients - Cong Lu; Li-Xi Li; Hai-Lin Dong; Qiao Wei; Zhi-Jun Liu; Wang Ni; Aaron D. Gitler; Zhi-Ying Wu (Journal of Molecular Medicine, 2018)

Phosphorus accumulation and sorption characteristics of P-enriched soils in the Dian Lake basin, southwestern China - Guo-Sheng Zhang; Jiang-Xue Xue; Zhen-Wei Ni; Jian-Cha Li (Journal of Soils and Sediments, 2018)

Investigation of Perfluoroalkyl Substances (PFASs) in Sediments from the Urban Lakes of Anqing City, Anhui Province, China - Fasong Li; Hanyu Huang; Zhibing Xu; Hui Ni; Hao Yan; Ran Chen; Yan Luo; Wei Pan; Jinyun Long; Xiaofang Ye; Xiaofen Qian; Guangming Yu (Bulletin of Environmental Contamination and Toxicology, 2017)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Rapid and sensitive detection of redspotted grouper nervous necrosis virus ( RGNNV ) infection by aptamer–coat protein–aptamer sandwich enzyme‐linked apta‐sorbent assay ( ELASA ) - L Zhou; P Li; S Ni; Y Yu; M Yang; S Wei; Q Qin (Journal of Fish Diseases, 2017)
Redspotted grouper nervous necrosis virus ( RGNNV ) is one of the most devastating pathogens in the aquaculture of the grouper, Epinephlus sp., worldwide. The early and rapid diagnosis of RGNNV is important for the prevention of RGNNV infection. In this study, an aptamer (A10)‐based sandwich enzyme‐linked apta‐sorbent assay ( ELASA ) was developed for RGNNV diagnosis. This sandwich ELASA showed high specificity for the RGNNV coat protein ( CP ) and virions in virus‐infected cells and tissues. At the optimized working concentration of 200 nM of aptamer, the ELASA could detect RGNNV in the lysates of as few as 4 × 10 3 RGNNV ‐infected GB cells. Incubation for 10 min was sufficient to produce accurate results. The sandwich ELASA was most stable at incubation temperatures of 4–25°C, but could still distinguish RGNNV ‐infected samples from the controls at 37°C. It could detect RGNNV infection in brain lysates diluted 1/10, with results consistent with those of reverse transcription PCR , although with 10% less sensitivity. The main equipment required includes dissection tools, a water bath, Pierce™ Streptavidin Coated Plates and a microplate reader. The sandwich ELASA has great potential utility for the rapid and sensitive diagnosis of RGNNV in its early stages by fish farmers.

Characterization of extracellular polymeric substance (EPS) fractions produced by Microcystis aeruginosa under the stress of linoleic acid sustained-release microspheres - Lixiao Ni; Danye Li; Shiyi Rong; Lili Su; Wei Zhou; Peifang Wang; Chao Wang; Shiyin Li; Kumud Acharya (Environmental Science and Pollution Research, 2017)

The complete mitogenome sequence of Tylototriton ziegleri (Amphibia: Caudata) - Ye Jiang; Zhimin Wei; Fuyao Han; Qingyong Ni; Yongfang Yao; Huailiang Xu; Ying Li; Dingqi Rao; Mingwang Zhang (Conservation Genetics Resources, 2017)

Complete mitochondrial genome of Trachypithecus poliocephalus (Primates: Cercopithecidae) - Dingju Wei; Yongfang Yao; Diyan Li; Qingyong Ni; Meng Xie; Mingwang Zhang; Yinglong Wu; Huailiang Xu (Conservation Genetics Resources, 2017)

More than meets the eye: The barrier effect of the Yangtze River outflow - Gang Ni; Elizabeth Kern; Yun‐Wei Dong; Qi Li; Joong‐Ki Park (Molecular Ecology, 2017)
The Yangtze (Changjiang) River enters the East China Sea with huge annual freshwater and sediment deposits. This outflow, known as the Changjiang diluted water ( CDW ), causes striking ecological gradients that potentially shape coastal species’ distribution and differentiation. The CDW has long been rendered as a marine biogeographic boundary separating cold‐temperature and warm‐water faunas, but it remains unclear whether and to what extent it acts as an intraspecific barrier. Here, we synthesize published phylogeographic studies related to the CDW to address these issues. We find that the influence of the CDW on population differentiation is taxonomically variable, and even congeneric species may respond differently. In studies that claim the CDW is a phylogeographic barrier, the underlying assumptions explaining observed genetic breaks are sometimes incorrect, and some may have misinterpreted results due to conceptual confusion or insufficient geographic sampling. After excluding these studies, the remaining ones generally show shallow genetic divergence but significant population structure for coastal species across the CDW , suggesting that the CDW has not been a historically persistent barrier, but rather has acted as a filter within some species recently, probably after the last glacial maximum.

Effects of biomass ash, bone meal, and alkaline slag applied alone and combined on soil acidity and wheat growth - Ren-yong Shi; Jiu-yu Li; Ni Ni; Khalid Mehmood; Ren-kou Xu; Wei Qian (Journal of Soils and Sediments, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Individual and combined inhibition of phenol and thiocyanate on microbial activity of partial nitritation - Qiong Guo; Zhi-Jian Shi; Chen-Chen Yang; Mei Huang; Jia-Li Xu; Yi-Qun Xu; Wei-Min Ni; Ren-Cun Jin (Environmental Science and Pollution Research, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Establishment and characterization of a cell line from the head kidney of golden pompano Trachinotus ovatus and its application in toxicology and virus susceptibility - P. Li; L. Zhou; S. Wei; M. Yang; S. Ni; Y. Yu; J. Cai; Q. Qin (Journal of Fish Biology, 2017)
A cell line derived from the head kidney of golden pompano Trachinotus ovatus ( TOHK ) was established and characterized in this study. The TOHK cells grew most rapidly at 28° C and the optimum foetal bovine serum concentration in L‐15 medium was 10%. The TOHK cells have a diploid chromosome number of 2 N = 54. The transfection efficiency of TOHK cells was 7·5% at the 15th passage and 72% at the 40th passage. The transfection efficiency in TOHK cells was high, so these cells are suitable for foreign gene expression. The cytotoxic effects of heavy metals and extracellular products from Vibrio anguillarum and Vibrio alginolyticus were demonstrated in TOHK cells, so this TOHK cell line could also be applied in environmental monitoring of heavy metals and pathogenic bacteria. TOHK cell line showed high virus susceptibility, such as grouper nervous necrosis virus (GNNV) and Singapore grouper iridovirus (SGIV). Then, TOHK cell line could be used for the study of viral pathogenesis and the development of antiviral strategies.

Sap flow-based transpiration in Phyllostachys pubescens: applicability of the TDP methodology, age effect and rhizome role - Zhao Xiu-hua; Zhao Ping; Zhang Zhen-zhen; Zhu Li-wei; Niu Jun-feng; Ni Guang-yan; Hu Yan-ting; Ouyang Lei (Trees, 2017)

Establishment and characterization of a mid-kidney cell line derived from golden pompano Trachinotus ovatus, a new cell model for virus pathogenesis and toxicology studies - Lingli Zhou; Pengfei Li; Jiaxin Liu; Songwei Ni; Yepin Yu; Min Yang; Shina Wei; Qiwei Qin (In Vitro Cellular & Developmental Biology - Animal, 2017)

Dissipation and phytoremediation of polycyclic aromatic hydrocarbons in freshly spiked and long-term field-contaminated soils - Ran Wei; Jinzhi Ni; Xiaoyan Li; Weifeng Chen; Yusheng Yang (Environmental Science and Pollution Research, 2017)

Activation of the TXNIP/NLRP3 inflammasome pathway contributes to inflammation in diabetic retinopathy: a novel inhibitory effect of minocycline - Wei Chen; Minjie Zhao; Shuzhi Zhao; Qianyi Lu; Lisha Ni; Chen Zou; Li Lu; Xun Xu; Huaijin Guan; Zhi Zheng; Qinghua Qiu (Inflammation Research, 2017)

Effects of hydrogeological properties on sea-derived benzene transport in unconfined coastal aquifers - Wei-Ci Li; Chuen-Fa Ni; Chia-Hsing Tsai; Yi-Ming Wei (Environmental Monitoring and Assessment, 2016)

Establishment and characterization of a novel cell line from the brain of golden pompano (Trachinotus ovatus) - Pengfei Li; Lingli Zhou; Songwei Ni; Meng Xu; Yepin Yu; Jia Cai; Shina Wei; Qiwei Qin (In Vitro Cellular & Developmental Biology - Animal, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Coupling analysis of China’s urbanization and carbon emissions: example from Hubei Province - Qi Li; Ya-Ni Wei; Yanfang Dong (Natural Hazards, 2016)

Water-CCUS nexus: challenges and opportunities of China’s coal chemical industry - Qi Li; Ya-Ni Wei; Zheng-Ao Chen (Clean Technologies and Environmental Policy, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

A newly isolated Haloalkaliphilic bacterium from middle–late Eocene halite formed in salt lakes in China - Fan-Wei Meng; Xiu-Qiang Wang; Pei Ni; Gunther Kletetschka; Chun-He Yang; Yin-Ping Li; Yong-Hua Yang (Carbonates and Evaporites, 2015)

Genetic diversity and evolution of two capsid protein genes of citrus tristeza virus isolates from China - Guan-Wei Wu; Min Tang; Guo-Ping Wang; Feng-Yin Jin; Zuo-Kun Yang; Li-Jing Cheng; Ni Hong (Archives of Virology, 2015)

Effects of extremely low frequency alternating-current magnetic fields on the growth performance and digestive enzyme activity of tilapia Oreochromis niloticus - Ying Li; Bixiao Ru; Xingfa Liu; Wei Miao; Kai Zhang; Lili Han; Haijun Ni; Hongjuan Wu (Environmental Biology of Fishes, 2015)

Management of differentiated thyroid carcinoma with bone metastasis: a case report and review of the Chinese literature - Wei-dong Zhang; Da-ren Liu; Cheng-cheng Feng; Chuan-biao Zhou; Chen-ni Zhan; Ri-sheng Que; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Spatial-temporal patterns of vegetation dynamics and their relationships to climate variations in Qinghai Lake Basin using MODIS time-series data - Wei Guo; Xiangnan Ni; Duanyang Jing; Shuheng Li (Journal of Geographical Sciences, 2014)

Screening essential genes of Mycobacterium tuberculosis with the pathway enrichment method - Guangyu Xu; Zhaohui Ni; Yue Shi; Xiaoyu Sun; Huaidong Wang; Chengguo Wei; Guoqing Wang; Fan Li (Molecular Biology Reports, 2014)

Neural Stem Cell Transplants Improve Cognitive Function Without Altering Amyloid Pathology in an APP/PS1 Double Transgenic Model of Alzheimer’s Disease - Wei Zhang; Pei-Jun Wang; Hong-ying Sha; Jiong Ni; Ming-hua Li; Guo-jun Gu (Molecular Neurobiology, 2014)

Hydrocarbon migration through salt: evidence from Kelasu tectonic zone of Kuqa foreland basin in China - Qin-Gong Zhuo; Fan-Wei Meng; Yan Song; Hai-Jun Yang; Yong Li; Pei Ni (Carbonates and Evaporites, 2014)

Autophagy Regulates Vascular Endothelial Cell eNOS and ET-1 Expression Induced by Laminar Shear Stress in an Ex Vivo Perfused System - Fengxia Guo; Xiaohong Li; Juan Peng; Yaling Tang; Qin Yang; Lushan Liu; Zuo Wang; Zhisheng Jiang; Ming Xiao; Chuyu Ni; Ruixing Chen; Dangheng Wei; et al. (Annals of Biomedical Engineering, 2014)

Identification and characterization of six cytochrome P450 genes belonging to CYP4 and CYP6 gene families in the silkworm, Bombyx mori - Bing Li; Hua Zhang; Min Ni; Bin-bin Wang; Fan-chi Li; Kai-zhun Xu; Wei-de Shen; Qing-you Xia; Ping Zhao (Molecular Biology Reports, 2014)

Early channel transurethral resection of the prostate for patients with urinary retention after brachytherapy - You-yun Zhang; Zhi-gen Zhang; Yan-lan Yu; Yi-cheng Chen; Kang-xin Ni; Ming-chao Wang; Wei-ping Zhao; Faisal Rehman; Shaw P. Wan; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

Bisoprolol reversed small conductance calcium-activated potassium channel (SK) remodeling in a volume-overload rat model - Yajuan Ni; Tingzhong Wang; Xiaozhen Zhuo; Bingxue Song; Jing Zhang; Feng Wei; Hongyuan Bai; Xuehui Wang; Dandan Yang; Li Gao; Aiqun Ma (Molecular and Cellular Biochemistry, 2013)

Effects of diethylhexyl phthalate (DEHP) given neonatally on spermatogenesis of mice - Xi-Feng Zhang; Teng Zhang; Liu Wang; Hong-Ying Zhang; Yong-De Chen; Xun-Si Qin; Yan-Min Feng; Yan-Ni Feng; Wei Shen; Lan Li (Molecular Biology Reports, 2013)

Vascular endothelial growth factor (VEGF) gene polymorphisms and risk of head and neck cancer: a meta-analysis involving 2,444 individuals - Wei-Dong Leng; Mei-Ni He; Qi-Lin Chen; Heng Gong; Li Zhang; Xian-Tao Zeng (Molecular Biology Reports, 2013)

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)

Functional polymorphisms in PIN1 promoter and esophageal carcinoma susceptibility in Chinese population - Yonghe You; Jieqiong Deng; Jian Zheng; Lan Jiang; Na Li; Hongchun Wu; Wei Li; Jiachun Lu; Yifeng Zhou; Bin Ni (Molecular Biology Reports, 2013)

Environmental Informatics for Solid and Hazardous Waste Management: Advances, Challenges, and Perspectives - Jia-Wei Lu; Ni-Bin Chang; Li Liao (Critical Reviews in Environmental Science and Technology, 2013)

Enhanced overall resistance to Fusarium seedling blight and Fusarium head blight in transgenic wheat by co-expression of anti-fungal peptides - Zheng-Wei Liu; He-Ping Li; Wei Cheng; Peng Yang; Jing-Bo Zhang; An-Dong Gong; Yan-Ni Feng; W. G. Dilantha Fernando; Yu-Cai Liao (European Journal of Plant Pathology, 2012)

Role of the EpCAM (CD326) in prostate cancer metastasis and progression - Jie Ni; Paul J. Cozzi; Wei Duan; Sarah Shigdar; Peter H. Graham; Kearsley H. John; Yong Li (Cancer and Metastasis Reviews, 2012)

Phylogenetic analysis of the bovine parainfluenza virus type 3 from cattle herds revealing the existence of a genotype A strain in China - Yong-Jun Wen; Xin-Chuan Shi; Feng-Xue Wang; Wei Wang; Shu-Qin Zhang; Guo Li; Ni Song; Li-Zhi Chen; Shi-Peng Cheng; Hua Wu (Virus Genes, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Adaptation of submerged macrophytes to both water depth and flood intensity as revealed by their mechanical resistance - Guorong Zhu; Wei Li; Meng Zhang; Leyi Ni; Shengrui Wang (Hydrobiologia, 2012)

Bisphenol A exposure modifies DNA methylation of imprint genes in mouse fetal germ cells - Xi-Feng Zhang; Lian-Jun Zhang; Yan-Ni Feng; Bo Chen; Yan-Min Feng; Gui-Jin Liang; Lan Li; Wei Shen (Molecular Biology Reports, 2012)

Identification and molecular evolutionary analysis of TLR5 gene from the Tibetan macaque (Macaca thibetana) - Ying Huang; Yong-Fang Yao; Yan Li; Qing-Yong Ni; Liang Zhou; Shuan-Ling Zhang; Wei Liu; Huai-Liang Xu (Genes & Genomics, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

A meta-analysis of HLA-DR polymorphism and genetic susceptibility to idiopathic dilated cardiomyopathy - Bo Jin; Xin-Ping Luo; Huan-Chun Ni; Wei Shen; Hai-Ming Shi; Yong Li (Molecular Biology Reports, 2012)

A meta-analysis of β1-adrenergic receptor gene polymorphisms in idiopathic dilated cardiomyopathy - Bo Jin; Qu-Zhen Ge-Shang; Yong Li; Wei Shen; Hai-Ming Shi; Huan-Chun Ni (Molecular Biology Reports, 2012)

Antioxidant effect of a phytoestrogen equol on cultured muscle cells of embryonic broilers - Xiao-Jing Wei; Jing Wu; Ying-Dong Ni; Li-Zhi Lu; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Two hydrothermal fields found on the Southern Mid-Atlantic Ridge - ChunHui Tao; HuaiMing Li; YaoMin Yang; JianYu Ni; RuYong Cui; YongShun Chen; JiaBiao Li; YongHua He; Wei Huang; JiJiang Lei; YeJian Wang (Science China Earth Sciences, 2011)

Varied association of prothrombin G20210A polymorphism with coronary artery disease susceptibility in different ethnic groups: evidence from 15,041 cases and 21,507 controls - Bo Jin; Yong Li; Qu-Zhen Ge-Shang; Huan-Chun Ni; Hai-Ming Shi; Wei Shen (Molecular Biology Reports, 2011)

Cytochrome P450 2C19 polymorphism is associated with poor clinical outcomes in coronary artery disease patients treated with clopidogrel - Bo Jin; Huan-Chun Ni; Wei Shen; Jian Li; Hai-Ming Shi; Yong Li (Molecular Biology Reports, 2011)

Rhodanobacter xiangquanii sp. nov., a Novel Anilofos-Degrading Bacterium Isolated from a Wastewater Treating System - Jun Zhang; Jin-Wei Zheng; Bao-Jian Hang; Ying-Ying Ni; Jian He; Shun-Peng Li (Current Microbiology, 2011)

Triggering of death receptor apoptotic signaling by human papillomavirus 16 E2 protein in cervical cancer cell lines is mediated by interaction with c-FLIP - Wei Wang; Yong Fang; Ni Sima; Yan Li; Wei Li; Li Li; Linfei Han; Shujie Liao; Zhiqiang Han; Qinglei Gao; Kezhen Li; Dongrui Deng; et al. (Apoptosis, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Scale effects of leaf area index inversion based on environmental and disaster monitoring satellite data - Hao Zhang; XiaoWen Li; ChunXiang Cao; Hua Yang; MengXu Gao; Sheng Zheng; Min Xu; DongHui Xie; HuiCong Jia; Wei Ji; Jian Zhao; Wei Chen; et al. (Science China Earth Sciences, 2010)

Evaluation of recombinant endostatin in the treatment of atherosclerotic plaques and neovascularization in rabbits - Wei Mao; Jing Kong; Jin Dai; Zhao-quan Huang; Dong-zhi Wang; Gui-bao Ni; Min-li Chen (Journal of Zhejiang University-SCIENCE B, 2010)

A new dinorclerone diterpenoid glycoside from Tinospora sinensis - Lang-Ping Dong; Chang-Xiang Chen; Wei Ni; Bai-Bo Xie; Jun-Zhu Li; Hai-Yang Liu (Natural Product Research, 2010)

Clear and independent associations of several HLA-DRB1 alleles with differential antibody responses to hepatitis B vaccination in youth - Yufeng Li; Rong Ni; Wei Song; Wenshuo Shao; Sadeep Shrestha; Sushma Ahmad; Coleen K. Cunningham; Patricia M. Flynn; Bill G. Kapogiannis; Craig M. Wilson; Jianming Tang (Human Genetics, 2009)

Losartan reduced connexin43 expression in left ventricular myocardium of spontaneously hypertensive rats - Li-li Zhao; Hong-juan Chen; Jun-zhu Chen; Min Yu; Yun-lan Ni; Wei-fang Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

RNA interference against HPV16 E7 oncogene leads to viral E6 and E7 suppression in cervical cancer cells and apoptosis via upregulation of Rb and p53 - Ni Sima; Wei Wang; Debo Kong; Dongrui Deng; Qian Xu; Jianfeng Zhou; Gang Xu; Li Meng; Yunping Lu; Shixuan Wang; Ding Ma (Apoptosis, 2008)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

Auxin Flow in Anther Filaments is Critical for Pollen Grain Development through Regulating Pollen Mitosis - Xiao-Li Feng; Wei-Min Ni; Stephan Elge; Bernd Mueller-Roeber; Zhi-Hong Xu; Hong-Wei Xue (Plant Molecular Biology, 2006)